Biodegradable polyester articles containing enzymes

By using liquid composition and low-temperature mixing process in plastics, the uniform distribution of biological enzymes is achieved, the problem of uneven distribution of enzymes in plastics is solved, and the mechanical properties and degradation efficiency of plastics are improved.

JP7627253B2Active Publication Date: 2025-02-05CARBIOLICE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022212427
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-08-31
Filing Date
2022-12-28
Publication Date
2025-02-05
Estimated Expiration
2038-08-31

Smart Images

  • Figure 0007627253000001
    Figure 0007627253000001
  • Figure 0007627253000002
    Figure 0007627253000002
  • Figure 0007627253000003
    Figure 0007627253000003
Patent Text Reader

Abstract

A novel biodegradable plastic article is provided, which comprises a polyester and a biological material capable of degrading the polyester, wherein the biological material is uniformly dispersed throughout the plastic article, and a method for producing the same. [Solution] A biodegradable plastic article comprising at least one polyester and a biological substance having polyester-degrading activity, wherein the biodegradable plastic article comprises a carrier selected from polysaccharides and, optionally, a carrier polymer having a melting temperature of less than 140°C and / or a glass transition temperature of less than 70°C, and the biological substance is capable of degrading the polyester and is uniformly dispersed throughout the plastic article.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel biodegradable plastic article comprising a polyester and a biological material capable of degrading the polyester, the biological material being uniformly dispersed throughout the plastic article. The present invention also relates to a method for producing the plastic article comprising the steps of mixing the biological material in a liquid composition or in a masterbatch and a selected carrier with a polyester. [Background technology]

[0002] To solve the environmental problems of plastics and the accumulation of plastic articles in landfills and natural habitats, and also to comply with restrictive legislation, especially for short-life products (e.g., bags, trays, containers, packaging including bottles, agricultural films, etc.), various biodegradable plastic compositions have been developed.

[0003] These plastic compositions generally contain polyesters, flours or starches derived from various cereals (US Pat. No. 5,739,244; US Pat. No. 6,176,915; US Patent Publication No. 2004 / 0167247; WO 2004 / 113433; FR 2 903 042; FR 2 856 405). Various solutions have been proposed to improve the control of the degradation of these plastics, by inorganic chemical additives (WO 2010 / 041063) or by the inclusion of biological substances capable of degrading the polyesters (WO 2013 / 093355; WO 2016 / 198652; WO 2016 / 198650; WO 2016 / 146540; WO 2016 / 062695). The resulting plastic article contains biological material, particularly enzymes, dispersed in the polymer and has improved biodegradability compared to plastic articles that do not contain such biological material.

[0004] Whereas the manufacture of articles comprising polyesters and enzymes has already been described, their implementation may result in technical problems related to the uniformity, surface roughness and mechanical properties of the resulting articles. Known or proposed manufacturing methods result in non-uniform articles exhibiting enzyme aggregates. The non-uniform distribution of the enzyme in the plastic composition has many drawbacks in terms of physical properties and aesthetics. In particular, thin films cannot be produced. In some instances, the degradation activity of biological materials may be affected by the above-mentioned conventional methods. Summary of the Invention

[0005] Thus, the present invention provides biodegradable plastic articles that exhibit uniform distribution of enzymes throughout the article and provide expected physical performance. The present invention also provides plastic articles with improved degradability.

[0006] The present invention provides novel biodegradable plastic articles that comprise at least one polyester and biological materials and that exhibit expected physical and degradative properties.

[0007] It is therefore an object of the present invention to provide a biodegradable plastic article comprising at least one polyester and a biological material having polyester-degrading activity, said biological material being capable of degrading said polyester and being uniformly dispersed in the plastic article.

[0008] The present invention provides a biodegradable plastic article comprising at least one polyester and a biological material having polyester-degrading activity, the biological material comprising a carrier selected from polysaccharides and optionally a polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C (carrier polymer), and mixtures thereof, said biological material being capable of degrading said polyester and being uniformly dispersed in the plastic article.

[0009] In particular, the present invention provides a method for manufacturing a plastic article comprising the steps of: - 10-98% polylactic acid (PLA) - 0-40% polysaccharides; - 0-40% of a carrier polymer, if one of the polysaccharide or the carrier polymer is 0% and the other is not 0%; - 0.01-10% of a biological substance with PLA degrading activity, uniformly dispersed in the plastic article; The present invention provides a plastic article comprising:

[0010] The present invention also relates to a method for preparing a plastic article comprising at least one polyester and a biological material having polyester-degrading activity, uniformly dispersed in the plastic article, the method comprising the steps of (a) mixing 0.01% to 10% by weight of the biological material having polyester-degrading activity with the at least one polyester, and (b) molding the mixture of step (a) in a plastic article, In step (a), the biological material is - a liquid composition comprising said biological material having polyester degrading activity, a carrier and water, or - a masterbatch comprising said polyester-degrading biological material and a carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C and mixing said biological material in a form suitable for uniformly dispersing said biological material in said plastic article, said biological material being selected from the group consisting of:

[0011] The invention also provides a method for improving the distribution uniformity of a biological material in a plastic article comprising a polyester, the method comprising introducing the biological material in the form of a liquid composition comprising a biological material having polyester-degrading activity, a carrier and water, or in the form of a masterbatch comprising a biological material having polyester-degrading activity and a carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C, in a process for producing such a plastic article.

[0012] The present invention also provides a masterbatch comprising a biological material having polyester degrading activity, a carrier polymer having a melting temperature below 140° C. and / or a glass transition temperature below 70° C., and optionally a polysaccharide. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention relates to novel plastic articles with improved uniform distribution of biological materials, particularly enzymes, and methods for their manufacture. The present invention shows that articles with an appropriate distribution of active biological materials are particularly valuable for meeting the physical and degradative properties expected of disposable, short-life plastic articles.

[0014] definition The present disclosure will be best understood with reference to the following definitions.

[0015] In the present invention, the term "plastic article" refers to any article made from at least one polymer, such as plastic sheets, films, tubes, rods, profiles, shapes, bulk blocks, fibers, etc. Preferably, the plastic article is an industrial product, such as rigid or flexible packaging, agricultural films, sacks (bags and sacks), disposable articles, etc. Preferably, the plastic article comprises a semi-crystalline and / or amorphous polymer, or a mixture of semi-crystalline polymers and additives. The plastic article may contain additional substances or additives, such as plasticizers, inorganic or organic fillers, etc. According to the present invention, the plastic article may be selected from a plastic film or a rigid plastic article.

[0016] According to the present invention, the term "plastic film" refers to a plastic flexible sheet (i.e., bendable without breaking) having a thickness of less than 250 μm. Thin films are considered to have a thickness of less than 100 μm, preferably less than 50 μm, and are preferably produced by blown film extrusion, while thick films have a thickness of more than 100 μm, and are preferably produced by cast film extrusion. Examples of plastic films include agricultural films, plastic bags (bags or sacks), flexible packaging films, food films, mailing films, liner films, multipack films, industrial films, personal care films, nets, etc.

[0017] According to the present invention, the term "rigid plastic article" refers to a plastic article that is not a film. These articles are preferably manufactured by calendaring, injection molding, thermoforming, blow molding, or by rotational molding and 3D printing. Examples of rigid plastic articles include thin-walled packaging such as food and beverage packaging, boxes, trays, containers, food service products, electronic device casings, cosmetic cases, outdoor gardening products such as pots, rigid packaging, containers, cards, cotton buds, irrigation pipes, etc. Some rigid plastic articles can be manufactured by thermoforming plastic sheets with a thickness of 250 μm or more, and such plastic sheets are manufactured by film casting or calendaring. According to the present invention, the rigid plastic article has a thickness of less than 5 mm, preferably less than 3 mm.

[0018] As used herein, the term "plastic composition" refers to a mixture of polymer and biological material, and finally additional compounds (e.g., additives, fillers, etc.), prior to any molding or conditioning steps to produce a plastic article. In a particular embodiment of the invention, the plastic composition is a masterbatch in solid form prior to incorporation into a polyester matrix.

[0019] "Polyester-based matrix" refers to a matrix that contains one or more polyesters as the main component. The polyester-based matrix contains at least 51% by weight, preferably at least 60% or 70% by weight of polymer, based on the total weight of the composition. The polyester-based matrix may further contain additional compounds, such as additives. According to the present invention, the polyester-based matrix does not contain biological materials.

[0020] As used herein, the term "masterbatch" refers to a concentrated mixture of a selected component (e.g., biological material, additive, etc.) and a polymer that can be used to introduce the selected component into a plastic article or composition to impart a desired property to the plastic article or composition. The masterbatch composition allows the processor to economically introduce the selected component during plastic production. Advantageously, the masterbatch is composed of a polymer in which the selected component is incorporated at a high concentration. Generally, the masterbatch is intended to be mixed with a polyester or polyester-based matrix to produce a final plastic containing the selected component in the desired amount. The masterbatch may further comprise an inorganic or organic filler. According to the present invention, the masterbatch comprises a composition of biological material having at least 5% polyester degradation activity. In the present invention, the polymer of the masterbatch is preferably selected from polymers having a melting temperature (Tm) of less than 140°C. For amorphous polymers, Tm refers to the transformation temperature at which the amorphous polymer is sufficiently fluid to be processed by extrusion (i.e., in a rubbery or softened state).

[0021] "Polymer" refers to a compound or mixture of compounds whose structure is composed of multiple repeating units linked by covalent chemical bonds. In the present invention, the term "polymer" includes natural or synthetic polymers containing a single type of repeating unit (i.e., homopolymers) or different types of repeating units (i.e., block and random copolymers). By way of example, synthetic polymers include petroleum-derived or bio-based polymers, such as polyolefins, aliphatic or aromatic polyesters, polyamides, polyurethanes, and polyvinyl chloride. Natural polymers include lignin, and polysaccharides, such as cellulose, hemicellulose, starch, and their derivatives, which may or may not be plasticized.

[0022] In the present invention, the term "polyester" refers to a polymer that contains an ester functionality in its backbone. The ester functionality is characterized by a carbon bonded to three other atoms (a single bond to carbon, a double bond to oxygen, and a single bond to oxygen). The single bonded oxygen bonds to another carbon. Depending on the composition of the backbone, the polyester can be aliphatic, aromatic, or semi-aromatic. The polyester can be a homopolymer or a copolymer. As an example, polylactic acid is an aliphatic homopolymer composed of one monomer, lactic acid, and polyethylene terephthalate is an aliphatic-aromatic copolymer composed of two monomers, terephthalic acid and ethylene glycol. Such polyesters can be natural or chemically modified. In the present invention, the term "filler" refers to a substance that is incorporated into a plastic composition and / or plastic article to reduce its cost or optionally improve its physical properties (e.g., its hardness, stiffness, or strength). Fillers can be inactive (i.e., inert) or active materials and can form chemical bonds with the components of the plastic composition or article. The fillers may be natural, synthetic or modified. The fillers may be selected from inorganic or organic fillers.In certain embodiments of the present invention, the inorganic filler is selected from the group consisting of calcite, carbonates or metal carbonates such as calcium carbonate (or limestone), potassium carbonate, magnesium carbonate, aluminum carbonate, zinc carbonate, copper carbonate, chalk, dolomite, silicates such as hydrous magnesium silicate, for example talc or soapstone, calcium silicate (wollastonite), potassium silicate, magnesium silicate (talc), aluminum silicate (kaolin), or mixtures thereof, for example mica, smectites such as montmorillonite, vermiculite, and palygorskite-sepiolite, sulfates such as barium sulfate, or calcium sulfate. (gypsum), mica, hydroxide salts or metal hydroxides, such as calcium hydroxide or potassium hydroxide (potash), or magnesium hydroxide or aluminum hydroxide or sodium hydroxide (caustic soda), hydrotalcite, metal oxides or oxide salts, such as magnesium oxide or calcium oxide or aluminum oxide or iron oxide or copper oxide, clay, asbestos, silica, graphite, carbon black, metal fibers or foils, glass fibers, magnetic fillers, aramid fibers, ceramic fibers and derivatives thereof or blends / mixtures of these materials. Alternatively or in addition, the organic filler is selected from the group consisting of wood flour, plant flour or vegetable flour, such as cereal flour (corn flour, wheat flour, rice flour, soybean flour, nut shell flour, clamshell flour, corn cob, cork flour, rice husk flour); sawdust; vegetable fibers, such as flax fiber, wood fiber, hemp fiber, bamboo fiber, chicken feathers and derivatives thereof, or blends / mixtures of these materials. Natural polymers can also be used as organic fillers, such as lignin, or polysaccharides, such as cellulose or hemicellulose, starch, chitin, chitosan and derivatives or blends / mixtures of these materials.

[0023] As used herein, the term "biological material" refers to active enzymes or enzyme-producing microorganisms, such as spore-forming microorganisms, as well as combinations thereof. According to the present invention, "biological material" preferably refers to enzymes. Biological material may be in the form of a solid (e.g., powder) or liquid.

[0024] In the present invention, the term "liquid composition" corresponds to a composition in fluid form, i.e. in the form of a container in which it is contained. In the present invention, the composition is in liquid form at room temperature and / or at the temperature of incorporation into a partially or completely melted polymer. As used herein, the term "polysaccharide" refers to a molecule composed of long chains of monosaccharide units linked together by glycosidic bonds. The structure of the polysaccharide may range from linear to highly branched. Examples include storage polysaccharides such as starch and glycogen and structural polysaccharides such as cellulose and chitin. Polysaccharides include natural polysaccharides or polysaccharides that have been chemically modified by crosslinking, oxidation, acetylation, partial hydrolysis, etc. Hydrocarbon polymers may be classified according to their source (marine, plant, microbial or animal), structure (linear, branched), and / or physical behavior (e.g., Gum or hydrocolloid designation, in which polysaccharides are hydrated in hot or cold water and formed at low concentrations Gum In the present invention, polysaccharides are classified according to the classification described in "Encapsulation Technologies for Active Food Ingredients and Food Processing -Chapter 3-Materials for Encapsulation- Christine Wandrey, Artur Bartkowiak, and Stephen E. Harding" as follows: starch and derivatives, such as amylose, amylopectin, maltodextrin, glucose syrup, dextrin, cyclodextrin, Cellulose and derivatives, such as methylcellulose, hydroxypropylmethylcellulose, ethylcellulose, etc. - Plant gums, including but not limited to gum arabic (or gum acacia), gum tragacanth, guar gum, locust bean gum, karaya gum, mesquite gum, galactomannan, pectin, soluble soy polysaccharides Gum Or natural Gum Plant exudates and extracts, also called - marine extracts, such as carrageenans and alginates, - microbial and animal polysaccharides, such as gellan, dextran, xanthan and chitosan may be classified as follows.

[0025] Polysaccharides can be further classified according to their solubility in water. In particular, cellulose is not soluble in water. According to the present invention, polysaccharides exhibit the ability to be soluble in water.

[0026] As used herein, the term "ambient temperature" or "room temperature" means a temperature between 10°C and 30°C, particularly between 20°C and 25°C.

[0027] As used herein, the term "soluble" refers to the ability of a solute (i.e., carrier, enzyme) to dissolve in a liquid solvent. The solubility of a substance depends on the physical and chemical properties of both the solute and the solvent, as well as the temperature, pressure, and pH of the solution, and may be defined according to international standards such as IUPAC. According to the IUPAC definition, solubility is the analytical composition of a saturated solution expressed as the percentage of a specified solute in a specified solvent. Solubility can be stated in various units of concentration, such as molar concentration, mass molality, mole fraction, mole ratio, mass (solute) per volume (solvent), and other units. Solubility is defined at a specific temperature and a specific atmospheric pressure. The degree of solubility ranges from infinitely soluble (unlimited) or completely miscible, such as ethanol in water, to sparingly soluble, such as silver chloride in water. The term "insoluble" is often applied to poorly soluble or very poorly soluble solutes. The term "maximum solubility" refers to the saturation concentration of a solute in a solvent, where additional amounts of solute do not thicken the solution and excess solute begins to precipitate. According to the present invention, maximum solubility refers to the saturation concentration of the carrier in the liquid composition, where other components, such as biological materials, may affect the solubility of the solute.

[0028] As used herein, the term "by weight" refers to an amount based on the total weight of the composition or product under consideration.

[0029] In the present invention, the term "about" refers to a margin of ±5%, preferably ±1%, or within the tolerance of an appropriate measuring device or instrument.

[0030] Uniformity of plastic articles The inventors have shown that the use of a liquid composition of biological material comprising a specific polysaccharide carrier in the manufacturing process can improve the degradability and physical and / or mechanical properties of plastic articles comprising polyesters and biological material with polyester-degrading activity, compared to the use of solid or liquid compositions of biological material in the art.

[0031] The inventors have found a way to reduce the surface roughness and ultimately the thickness of plastic articles without performing vigorous and expensive grinding operations on solid compositions. Furthermore, liquid compositions reduce the risk of inhaling particles of solid compositions during the manufacturing process of plastic articles, since the pulverence of the components is reduced compared to solid compositions. The inventors have found that the manufacture of plastic articles using biological materials, preferably in the form of liquid compositions, together with certain carriers, results in plastic articles with enhanced uniformity of dispersion of the biological materials in the plastic articles, and therefore improved physical properties, compared to plastic articles manufactured using biological materials in solid or liquid form in the art. The inventors have also found that the selection of the carrier is important to protect the biological materials during the manufacturing process, resulting in plastic articles with expected degradative and technical performance.

[0032] It is therefore an object of the present invention to provide a biodegradable plastic article comprising at least one polyester and a biological material having polyester-degrading activity, said biological material being capable of degrading said polyester and being uniformly dispersed in said plastic article.

[0033] Yet another object of the present invention is to provide a method for homogenizing the distribution of a biological substance in a plastic article comprising at least one polyester and a biological substance that degrades the polyester, the method comprising introducing the biological substance, preferably in the form of a liquid composition, together with a specific carrier, during the manufacturing process of the plastic article.

[0034] The uniformity of the distribution of biological material in the plastic article of the present invention can be evaluated by a person skilled in the art according to a method known per se in the art.For example, in the present invention, the uniformity of the distribution of biological material in the plastic article can be evaluated by measuring at least one of the following properties: haze, surface roughness, dynamic friction coefficient, Young's modulus, elongation at break, tensile stress at break, maximum stress, strain at maximum stress, impact strength and biodegradability.

[0035] Haze is defined as the percentage of incident light that is scattered beyond 2.5° through a plastic article. Haze is caused by impurities contained in the plastic article (such as the accumulation of small particles within the article or very small defects on the surface) or by its crystallinity. The lower the haze value, the more transparent the article. Haze has no specific unit and is expressed as a percentage. If the haze value is greater than 30%, the article is diffuse. Haze meters and spectrophotometers can be used to measure the level of haze. The haze of a plastic article can be measured according to ASTM D1003 or NF EN2155-9. According to the present invention, the haze of an article is measured according to NF EN2155-9 (August 1989). In particular, the plastic article of the present invention produced from a liquid composition of biological material may exhibit a lower haze value than the same plastic article produced from a solid composition of biological material. Typically, the plastic articles of the present invention exhibit haze values ​​that are about 1%, 2%, 3%, 4%, 5% or more lower than the haze values ​​of plastic articles made using solid compositions of biological material.

[0036] Young's modulus (also known as elastic modulus or tensile modulus) of a plastic article is a measure of the stiffness of a solid material. Stiffness is a mechanical property of a linear elastic solid material. Stiffness defines the relationship between stress (force per unit area) and strain (proportional deformation) of a material. The result is expressed in pascals or megapascals (MPa).

[0037] The elongation at break or strain at break of a plastic article relates to the ability of the plastic article to resist a change in shape without fracturing. Elongation at break is also known as fracture strain or tensile elongation at break. Elongation at break is measured in % and can be calculated by dividing the elongation at break of the plastic article by the initial gauge length of the plastic article and multiplying by 100.

[0038] The tensile stress at break (also known as stress at break or tensile strength at break) of a plastic article is defined as the tensile stress at the point where the specimen breaks. The tensile stress, also known as the ultimate tensile stress or maximum stress, corresponds to the maximum tensile stress that the specimen sustains during the tensile test. The results are expressed as force per unit area, usually megapascals (MPa).

[0039] Strain at maximum stress or tensile strength is the tensile strain at the point corresponding to the tensile strength. It is measured in % and can be calculated by dividing the elongation at maximum stress of the plastic article by the initial gauge length of the plastic article and multiplying by 100.

[0040] The Young's modulus, elongation at break, tensile stress at break, maximum stress and strain at maximum stress of plastic articles can be measured according to ASTM D882-12 or NF EN ISO527-3 for plastic articles having a thickness of less than 1 mm. This can be measured in two different directions, in particular the machine direction or the cross direction. The determination of these criteria for plastic articles having a thickness of 1 mm to 14 mm is carried out using ASTM D638-14 or NF EN ISO527-2.

[0041] In particular, the plastic articles of the invention obtained by using a liquid composition of biological material can exhibit a higher elongation at break than the same plastic article produced from a solid composition of biological material.Typically, the plastic articles of the invention are plastic films, which exhibit an elongation at break in at least one direction selected from the machine direction or the cross direction that is 10% higher, preferably 20%, 50%, 100% or more higher than the elongation at break of plastic articles produced using a solid composition of biological material.

[0042] In particular, the plastic article of the present invention produced using a liquid composition of biological material can exhibit a higher tensile stress at break than the same plastic article produced from a solid composition of biological material. Typically, the plastic article of the present invention is a plastic film and exhibits a tensile stress at break that is 20% higher, preferably 30%, 40%, 50% or more higher than the tensile stress at break of the plastic article produced using a solid composition of biological material. Typically, the plastic article of the present invention exhibits a tensile stress at break that is 5 MPa higher, preferably 7 MPa, 10 MPa, 15 MPa or more higher in at least one direction selected from the machine direction or the cross direction, than the tensile stress at break of the plastic article produced from a solid composition of biological material.

[0043] In particular, the plastic article of the present invention produced from a liquid composition of biological material can exhibit a higher Young's modulus than the same plastic article produced from a solid composition of biological material.Typically, the plastic article of the present invention is a plastic film and exhibits a Young's modulus of about 20% higher, preferably 30%, 40%, 50% or more higher, in at least one direction selected from the machine direction or the cross direction, than the plastic article produced from a solid composition of biological material.Typically, the plastic article of the present invention is a plastic film and exhibits a Young's modulus of about 20 MPa higher, preferably 30 MPa, 50 MPa, 100 MPa or more higher, in at least one direction selected from the machine direction or the cross direction, than the plastic article produced from a solid composition of biological material.

[0044] Coefficient of dynamic friction or coefficient of sliding friction or coefficient of kinetic friction (μ D A friction coefficient (also abbreviated as μ ) occurs when two objects move relative to each other and rub against each other (like a sled on the ground). Dis measured when a plastic article is sliding over another identical plastic article. The sliding friction coefficient is defined as the ratio of the dynamic friction force exerted by the plastic articles (the force required to overcome the friction) to the normal force N acting perpendicular to both plastic articles. This coefficient has no units. The surfaces to be tested are placed in planar contact with uniform contact pressure (normal force N). The force required to move the surfaces relative to each other is recorded (dynamic friction force). According to the invention, μ D is measured according to the standard NF EN ISO-8295 (December 2004) which is adapted for plastic films or sheets having a thickness of less than 0.5 mm. The apparatus comprises a horizontal test stand on which the plastic article of the invention is placed, a mass which generates a pressing force (1.96 N) and to which the plastic article is attached, and a traction mechanism which generates a relative movement between the mass and the test stand. According to the invention, the mass is pulled and moved on the test stand (test speed = 500 mm / min). The measurement value is accurate to about 0.01%. In particular, the plastic article of the invention made from a liquid composition of biological material can exhibit a lower dynamic friction coefficient than the same plastic article made from a solid composition of biological material. Typically, the plastic article of the invention is a plastic film and exhibits a dynamic friction coefficient that is 5% lower, preferably 10%, 15%, 20% or more lower than the dynamic friction coefficient of the plastic article made from a solid composition of biological material.

[0045] The surface roughness of the plastic article can be evaluated by visual inspection of a panel of users. The plastic article of the present invention shows no visible defects on its surface and is smooth. The plastic article made from the solid composition shows surface irregularities due to particle agglomerates that can be felt by touch and seen by the naked eye. This is also evaluated by measuring the thickness using a Mitutoyo thickness gauge, which demonstrates the presence of agglomerates in the plastic article.

[0046] Impact strength is defined as the resistance of a material to fracture under a stress applied at high speed, and is defined by the amount of energy absorbed before fracture. For rigid plastic articles, impact strength can be measured according to standard NF EN ISO179 using a plastic test piece 4 mm thick and 80 mm long made of the same material as the plastic article. The impact strength of rigid plastic articles with a thickness of less than 4 mm can also be measured directly on the plastic article according to standard NF EN ISO6603-1. In particular, the plastic article of the present invention obtained by using a liquid composition of biological material can exhibit a higher impact strength than the same plastic article produced from a solid composition of biological material. Typically, the plastic article of the present invention exhibits an impact strength about 20% higher, preferably 25%, 30%, 40% higher than the impact strength of a plastic article produced from a solid composition of biological material.

[0047] The inventors have also shown that in the manufacturing process of the plastic article of the invention, the introduction of the biological material by means of a liquid or solid composition, preferably a liquid composition, comprising the biological material and a selected carrier does not affect the technical performance of said plastic article compared to a plastic article not containing the biological material.

[0048] The present invention also provides a method for improving the biodegradability of the plastic article of the present invention, which comprises introducing a biological material composition with a selected carrier in the manufacturing process of the plastic article. The biodegradability is further improved by introducing a biological material liquid composition with a selected carrier in the manufacturing process of the plastic article. The biodegradability of the plastic article is defined as the release of monomers, dimers, or water and carbon dioxide over a defined period of time under aqueous conditions. In particular, according to the present invention, the biodegradability of the plastic article containing PLA is measured according to the release of lactic acid and dimers of lactic acid. In particular, the plastic article of the present invention obtained by using the biological material liquid composition can exhibit a higher biodegradability than the same plastic article produced from a biological material solid or liquid composition in the art. Typically, the plastic article of the present invention exhibits a biodegradability after 2 days that is about 100% higher, preferably 25%, 30%, 40% higher than the biodegradability of the plastic article produced from a biological material solid or liquid composition in the art.

[0049] In certain embodiments, the plastic article of the present invention is a plastic film that comprises at least one polyester and a biological material capable of degrading the polyester.

[0050] According to a preferred embodiment, the plastic film of the present invention is a film having a thickness of less than 100 μm, preferably less than 50 μm, more preferably less than 30 μm, even more preferably less than 20 μm.

[0051] In particular, the plastic film of the present invention exhibits a haze value that is about 3%, 4%, 5% or more lower than the haze value of plastic films made from solid compositions of biological materials. Thus, the haze value of the plastic film is 80% to 95%, preferably 85% to 93%. Alternatively, the haze value of the plastic film is greater than 30%, preferably greater than 50%, more preferably greater than 70%, even more preferably greater than 85%. Also, the haze value of the plastic film is less than 98%, preferably less than 96%, more preferably less than 95%, even more preferably less than 94%. In another embodiment, the haze value of the plastic film is less than 60%.

[0052] In another particular embodiment, the Young's modulus of the film is preferably greater than 200 MPa in both directions (machine direction or transverse direction), and / or the tensile stress at break of the film is preferably greater than 15 MPa in both directions (machine direction or transverse direction), and / or the elongation at break of the film is preferably greater than 130% in the machine direction and greater than 300% in the transverse direction. In another particular embodiment, the film according to the invention has an elongation at break of greater than 130% in the longitudinal direction and greater than 240% in the transverse direction, measured according to EN ISO527-3, and / or a tear strength of greater than 30 N / mm in the transverse direction of the film, measured according to EN ISO6383-1, while having a high PLA content. The film according to the invention also has a modulus of elasticity of greater than 200 MPa in the longitudinal direction and greater than 150 MPa in the transverse direction, measured according to EN ISO527-3, and / or a maximum stress of greater than 15 MPa in the longitudinal direction and greater than 13 MPa in the transverse direction, measured according to EN ISO527-3.

[0053] In another particular embodiment, the plastic article of the present invention is a rigid plastic article comprising at least one polyester and a biological material capable of degrading the polyester.

[0054] In a particular embodiment, the rigid plastic article of the present invention has a thermal resistance of 17 kJ / m according to NF EN ISO 179. 2 More than 20 kJ / m 2 In another particular embodiment, the rigid plastic article of the present invention exhibits a tensile modulus (elasticity modulus) according to NF EN ISO527-2 of less than 4 GPa, preferably less than 3 GPa, and a tensile strength at break of more than 40 MPa, preferably more than 55 MPa.

[0055] According to a particular embodiment, the rigid plastic article of the present invention is a sheet having a thickness of less than 800 μm, preferably less than 450 μm. The sheet of the present invention exhibits an impact strength according to NF EN ISO7765-1 of more than 1 J, preferably more than 1.5 J, more preferably more than 2 J. The elastic modulus of the sheet is less than 2 GPa in both directions (machine direction and transverse direction) while maintaining sufficient stiffness for the intended application, and the strain at maximum stress of the sheet is more than 3% in both directions, preferably more than 4%.

[0056] In another particular embodiment, the plastic article of the present invention is a nonwoven fabric comprising at least one polyester and a biological material capable of degrading said polyester.

[0057] Advantageously, the plastic article is a biodegradable plastic article according to at least one of the relevant standards and / or labels known to those skilled in the art, such as standard EN13432, standard NFT51800, standard ASTM D6400, OK Biodegradation Soil (TUV Austria label), OK Biodegradation Water (TUV Austria label), OK Compost (TUV Austria label), OK Compost Home (TUV Austria label).

[0058] Biodegradable plastic articles refer to plastics that are at least partially converted under environmental conditions into oligomers and / or monomers of at least one polyester of the plastic article, water, carbon dioxide or methane, and biomass. For example, the plastic article is biodegradable in water. Preferably, about 90% by weight of the plastic article is biodegraded in water within 90 days, more preferably within 60 days, and even more preferably within 30 days. More preferably, the plastic article can be biodegraded when exposed to moisture and temperature conditions occurring in the landscape. Preferably, about 90% by weight of the plastic article is biodegraded in the environment within 3 years, more preferably within 2 years, and even more preferably within 1 year. Alternatively, the plastic article may be biodegraded under industrial composting conditions where the temperature is maintained above 50°C.

[0059] The present invention also provides a method for enhancing the biodegradability of a plastic article comprising at least one polyester, the method comprising the steps of mixing a polyester with both a biological material suitable for degrading the polyester and an acid-resistant filler to obtain a plastic composition, and using the plastic composition to manufacture a plastic article.

[0060] Plastic article components It is an object of the present invention to provide a plastic article comprising at least one polyester chosen from copolymers of lactic acid and / or succinic acid and / or terephthalic acid or mixtures thereof.

[0061] Advantageously, the plastic article comprises at least one polyester selected from polylactic acid (PLA) (e.g. poly(L-lactic acid) (PLLA), poly(D-lactic acid) (PDLA), poly(D,L-lactic acid) (PDLLA) or PLA stereocomplex (scPLA)), polyglycolic acid (PGA), polyhydroxyalkanoates (PHA), polycaprolactone (PCL), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), and derivatives or blends / mixtures thereof. In a preferred embodiment, the plastic article comprises at least PLA and / or PCL and / or PBAT, more preferably at least PLA. In another embodiment, the polyester is selected from copolymers of lactic acid and / or succinic acid and / or terephthalic acid.

[0062] Preferably the polyester has a melting temperature above 140°C.

[0063] In another particular embodiment, the plastic article comprises at least two polyesters selected from polylactic acid (PLA), polyglycolic acid (PGA), polyhydroxyalkanoate (PHA), polycaprolactone (PCL), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), and derivatives or blends / mixtures thereof. In a preferred embodiment, the plastic article comprises at least two polyesters selected from PLA and / or PCL and / or PBAT, more preferably PLA and PBAT, or PLA and PCL.

[0064] In certain embodiments, the plastic article may further comprise at least one natural polymer. The natural polymer may be selected from the group of lignin, polysaccharides such as cellulose or hemicellulose, starch, chitin, chitosan, and derivatives or blends / mixtures thereof. In certain embodiments, the natural polymer is plasticized (e.g., with water or a plasticizer such as glycerol) before being used to prepare the masterbatch composition. Such a plasticization step modifies the chemical structure of the natural polymer, making it usable in the plastic manufacturing process. Preferably, the plastic article is made of cellulose, starch, flour, Gum and derivatives. More preferably, the plastic article of the present invention further comprises at least starch or flour, even more preferably a plasticized starch or flour. In particular, the starch is plasticized with glycerol.

[0065] The plastic article of the present invention further comprises a carrier selected from polysaccharides and optionally carrier polymers having a melting temperature below 140° C. and / or a glass transition temperature below 70° C., and mixtures thereof.

[0066] Preferably, the plastic article of the present invention further comprises a polysaccharide carrier and optionally a carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C.

[0067] More preferably, the plastic article of the present invention further comprises a polysaccharide carrier and a carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C.

[0068] The polysaccharide carrier is preferably a starch derivative, natural Gum , marine extracts, microbial and animal polysaccharides. In particular, such polysaccharides are starch derivatives, preferably maltodextrin. Alternatively, such polysaccharides are naturally occurring. Gumand preferably selected from gum arabic, guar gum, gum tragacanth, gum karaya, and even more preferably selected from gum arabic. Alternatively, such polysaccharides are marine extracts, preferably selected from carrageenans or alginates. Alternatively, such polysaccharides are microbial polysaccharides, preferably xanthan. Alternatively, such polysaccharides are animal polysaccharides, preferably chitosan.

[0069] In a particular embodiment, the carrier polymer having a melting temperature of less than 140°C and / or a glass transition temperature of less than 70°C is preferably a polyester selected from polycaprolactone (PCL), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), polyhydroxyalkanoate (PHA), polylactic acid (PLA), or a copolymer. In another particular embodiment, the carrier polymer is a natural polymer, preferably selected from starch. In another particular embodiment, the carrier polymer is a "universal" polymer, i.e., a polymer compatible with a wide range of polymers, such as copolymers (e.g., ethylene vinyl acetate copolymer, EVA).

[0070] Preferably, the carrier polymer as defined above has a melting temperature below 120° C. and / or a glass transition temperature below 30° C. For example, such a carrier polymer is selected from the group consisting of PCL, PBAT, PLA and EVA. Preferably, the carrier polymer is selected from the group consisting of PCL, PBAT and PLA. An advantage of such an embodiment is that it reduces heating of the biological material during the masterbatch manufacturing process.

[0071] In certain embodiments, the plastic article of the present invention comprises PLA, at least one additional polyester selected from PBAT and / or PCL, and at least one natural polymer selected from plasticized starch or flour.

[0072] According to another particular embodiment, the plastic article of the invention may further comprise one or more fillers. The fillers may be selected from any conventional fillers used in the plastics industry. The fillers may be natural or synthetic. The fillers may be selected from inorganic or organic fillers. In a preferred embodiment, the inorganic fillers are selected from calcite, carbonates or metal carbonates such as calcium carbonate (or limestone), potassium carbonate, magnesium carbonate, aluminum carbonate, zinc carbonate, copper carbonate, chalk, dolomite, silicates such as hydrous magnesium silicate, for example talc or soapstone, calcium silicate (wollastonite), potassium silicate, magnesium silicate (talc), aluminum silicate (kaolin), or mixtures thereof, for example mica, smectites such as montmorillonite, vermiculite, and palygorskite-sepiolite, sulfates such as barium sulfate, or calcium sulfate (sepiolite). The organic filler is selected from the group consisting of, but not limited to, wood flour, plant flour or vegetable flour, such as cereal flour (corn flour, wheat flour, rice flour, soy flour, nut shell flour, clamshell flour, corn cob, cork flour, rice husk flour); sawdust; plant fibres, such as flax fibre, wood fibre, hemp fibre, bamboo fibre, chicken feathers and their derivatives, or blends / mixtures of these materials. Natural polymers can also be used as organic fillers, such as lignin, or polysaccharides, such as cellulose or hemicellulose, starch, chitin, chitosan and derivatives or blends / mixtures of these materials.The type and exact amount of filler can be adapted by the skilled artisan depending on the type of plastic article and following the guidance provided in this application. Advantageously, the plastic article comprises at least one filler selected from calcium carbonate, talc or silica.

[0073] According to another particular embodiment, the plastic article of the present invention may further comprise one or more additives. Generally speaking, additives are used to improve certain properties of the final product (i.e. the final plastic article made with said masterbatch composition). For example, the additives may be selected from the group consisting of plasticizers, colorants, processing aids, slip agents, rheological agents, antistatic agents, anti-UV agents, toughening agents, impact modifiers, anti-fog agents, compatibilizers, flame retardants, antioxidants, light stabilizers, oxygen scavengers, inks, adhesives, fertilizers, and phytosanitary products, but are not limited thereto. Advantageously, the plastic article comprises at least one additive selected from plasticizers, slip agents and light stabilizers. Advantageously, the plastic article comprises less than 20% by weight of additives, preferably less than 10%, more preferably less than 5%, typically between 0.1 and 4% by weight of additives.

[0074] Advantageously, the plastic article of the present invention comprises, based on the total weight of the plastic article: - 10 to 98% of the above polyesters, in particular polylactic acid (PLA), - 0.01 to 10% of the above polysaccharide carrier, - 0 to 30% of the above-mentioned carrier polymers having a melting temperature below 140 ° C and / or a glass transition temperature below 70 ° C, - Biological substances with 0.01-10% PLA decomposition activity Includes.

[0075] Preferably, the plastic article comprises at least 3% carrier polymer, more preferably at least 4% carrier polymer. In another preferred embodiment, the plastic article comprises 0.1% to 1% polysaccharide carrier. In another preferred embodiment, the plastic article comprises less than 1%, preferably less than 0.5%, preferably about 0.25% biological material with PLA degrading activity.

[0076] In a particular embodiment, the plastic article comprises an enzyme having a PLA degrading activity of 0.1-0.5%, preferably about 0.25%.

[0077] In certain embodiments, the plastic article of the present invention comprises, based on the total weight of the plastic article: - 10 to 94% of the above polyesters, in particular polylactic acid (PLA), - 0.1 to 5% of the above polysaccharide carrier, - 4 to 20% of the above-mentioned carrier polymers having a melting temperature below 140 ° C and / or a glass transition temperature below 70 ° C, - Biological substances with 0.01-1% PLA decomposition activity Includes.

[0078] Other compositions of the present invention are described below. Although not mentioned, all other compositions additionally contain less than 5% of the above polysaccharide carrier, especially 0.1-1% of the polysaccharide carrier; and The second polyester and / or the natural polymer meet the characteristics that they can correspond to a carrier polymer or an additional polymer. In addition, a carrier polymer as defined above may also be included and can be referred to as a second polyester or a third polyester.

[0079] In certain embodiments, the plastic article of the present invention comprises, based on the total weight of the plastic article: - 10~98% PLA, - 0~70% secondary polyester, - 0-40% natural polymers; - 1-20% additives; - 0-40% of at least one filler, - a biological material having a PLA degrading activity of 0.01-10%; Includes.

[0080] In certain embodiments, the plastic article of the present invention comprises, based on the total weight of the plastic article: - 10~98% PLA, - 0-50% of a second polyester, preferably chosen from PBAT, - 0.1 to 10% of a third polyester, preferably chosen from polymers having a melting temperature below 140°C; - 0-40% natural polymers; - 1-20% additives; - 0-40% of at least one filler, - Biological substances with 0.01-10% PLA decomposition activity Includes.

[0081] In certain embodiments, the plastic article is a plastic film. Preferably, the plastic film of the present invention comprises, based on the total weight of the plastic film: - 10-60%, preferably 20-40% PLA, - 10 to 60%, preferably 20 to 40%, of a second polyester, preferably chosen from PBAT, - 0 to 40%, preferably 0 to 30%, of a natural polymer, preferably chosen from starch; - 1 to 20% of an additive, preferably chosen from plasticizers or compatibilizers, - 0.1 to 10% of at least one filler, preferably chosen from calcium carbonate, - Biological substances with 0.01-10% PLA decomposition activity Includes.

[0082] In another specific embodiment, the plastic film of the present invention comprises, based on the total weight of the plastic film, - 10-60%, preferably 20-40% PLA, - 10 to 60%, preferably 20 to 40%, of a second polyester, preferably chosen from PBAT, - 1 to 20% of an additive, preferably chosen from plasticizers or compatibilizers, - Biological substances with 0.01-10% PLA decomposition activity Includes.

[0083] In another specific embodiment, the plastic film of the present invention comprises, based on the total weight of the plastic film, - 10-60%, preferably 20-40% PLA, - 10 to 60%, preferably 20 to 40%, of a second polyester, preferably chosen from PBAT, - with 0~10% tertiary polyester, - 1 to 20% of an additive, preferably chosen from plasticizers or compatibilizers, - Biological substances with 0.01-10% PLA decomposition activity Includes.

[0084] In another specific embodiment, the plastic film of the present invention comprises, based on the total weight of the plastic film, - 10-60%, preferably 20-40% PLA, - 10 to 60%, preferably 20 to 40%, of a second polyester, preferably chosen from PBAT, - 0-10% of a third polyester, preferably chosen from PCL; - 1 to 40%, preferably 10 to 30%, of a natural polymer, preferably chosen from starch; - 1 to 20% of an additive, preferably chosen from plasticizers or compatibilizers, - 0.1 to 10% of at least one filler, preferably chosen from calcium carbonate, - Biological substances with 0.01-10% PLA decomposition activity Includes.

[0085] In a particular embodiment, the film of the present invention has a thickness of 15 μm to 30 μm and comprises at least 10% to 40% PLA, 5% to 15% PCL, and 40% to 70% PBAT based on the total weight of the plastic film. Advantageously, such a film has a higher depolymerization rate than a film without a carrier polymer such as a polysaccharide carrier and / or PCL, while maintaining a good elongation at break of more than 140% in MD for its application.

[0086] In certain embodiments, the rigid plastic article of the present invention comprises, based on the total weight of the plastic article: - 10~98% PLA, - 0~60% second polyester, - 0-20% additives, - 0-40% of at least one filler, - a biological material having a PLA degrading activity of 0.01-10%; Includes.

[0087] In a preferred embodiment, the plastic article of the present invention is made from the rigid plastic sheet of the present invention. Preferably, the rigid plastic sheet of the present invention has a plastic weight of: - 10-98%, preferably 50-95% PLA, - 0 to 30% of a second polyester, preferably chosen from PCL, which improves the impact strength, - 0 to 20% of additives, preferably chosen from plasticizers, impact modifiers and nucleating agents; - 0 to 40% of at least one filler, preferably chosen from calcium carbonate; - Biological substances with 0.01-10% PLA decomposition activity Includes.

[0088] In certain embodiments, the rigid plastic article of the present invention comprises, based on the total weight of the plastic article: - 10~98% PLA, - 0~50% second polyester, - With 0~20% tertiary polyester, - 0-40% natural polymers; - 0-20% additives, - 0-40% of at least one filler, - a biological material having a PLA degrading activity of 0.01-10%; Includes.

[0089] In a particular embodiment, the rigid plastic article of the present invention comprises more than 90% PLA based on the total weight of the plastic article and exhibits an impact strength of more than 1 J. In another particular embodiment, the plastic article of the present invention is obtained by using a liquid composition of biological material and from a master batch comprising 80% PCL. Thus, the plastic article comprises at least 4% PCL and exhibits an impact strength of more than 2 J and an elongation at break of more than 6%, preferably more than 15%, while maintaining a good stiffness of more than 1.6 GPa for its application.

[0090] biological material According to the invention, the plastic article comprises a biological material suitable for degrading at least one polyester contained in the plastic article. In another particular embodiment, the plastic article comprises a biological material suitable for degrading at least two polyesters contained in the plastic article.

[0091] In a preferred embodiment, the biological material comprises an enzyme having at least polyester degrading activity and / or a microorganism expressing and optionally secreting an enzyme having at least polyester degrading activity. In a preferred embodiment, the biological material consists of an enzyme having at least polyester degrading activity. In another particular embodiment, the biological material comprises or consists of at least two enzymes having polyester degrading activity. Examples of suitable enzymes having polyester degrading activity for use in the present invention include, but are not limited to, depolymerase, esterase, lipase, cutinase, carboxylesterase, protease, or polyesterase. In a particular embodiment, the biological material comprises or consists of an enzyme having PLA degrading activity. The biological material is preferably a protease selected from Amycolatopsis spp., Amycolatopsis orientalis, Proteinase K from Tritirachium album, Actinomadura keratinilytica, Laceyella sacchari LP175, Thermus spp., Bacillus licheniformis, Bacillus thermoproteolyticus or any commercially available enzyme known to degrade PLA, such as Savinase®, Esperase®, Everlase®, Protex®, Optimase®, Multifect®, or any enzyme of the subtilisin CAS9014-01-1 family or a functional variant thereof.

[0092] The enzymes may be in pure or concentrated form, or in admixture with other excipients or diluents. Combinations of enzymes may be used as well.

[0093] In an alternative embodiment, the biological material comprises a microorganism that produces such an enzyme, either naturally or as a result of specific manipulation (e.g., a recombinant microorganism). Preferred examples of suitable microorganisms include, but are not limited to, bacteria, fungi, and yeast. In one embodiment, the biological material comprises spore-forming microorganisms and / or their spores.

[0094] In certain embodiments, the biological material includes enzymes encapsulated in nanocapsules, enzymes encapsulated in cage molecules, and aggregated enzymes. The term "cage molecules" refers to molecules that can be inserted into the structure of the enzymes to stabilize them and make them resistant to high temperatures. Encapsulation techniques are well known to those skilled in the art and include, for example, nanoemulsions.

[0095] In certain embodiments, the plastic article comprises less than 11% by weight, preferably between 0.01% and 10% by weight, of biological material based on the total weight of the plastic article.

[0096] The biological material may be provided in liquid or solid form. For example, the biological material may be in powder form. In certain embodiments, the biological material used to prepare the plastic article is a liquid composition of enzymes and / or microorganisms mixed with a diluent or carrier, such as a stabilizing and / or solubilizing component. For example, the composition may be a solution containing the enzymes and / or microorganisms in suspension in water, and optionally additional components, such as glycerol, sorbitol, dextrin, starch, glycols such as propanediol, salts, etc.

[0097] According to the present invention, the biological material used to prepare the plastic article is provided under a liquid composition comprising said biological material having polyester degrading activity, a carrier and an aqueous solvent, the carrier being a starch derivative, natural Gum The polysaccharide is selected from marine extracts, microbial and animal polysaccharides.

[0098] Method for manufacturing plastic articles The present invention also relates to a method for preparing a plastic article comprising at least one polyester and a biological material having polyester degrading activity, uniformly dispersed in the plastic article, the method comprising the steps of (a) mixing 0.01% to 10% by weight of the biological material having polyester degrading activity with the at least one polyester, and (b) molding the mixture of step (a) in a plastic article, In step (a), the biological material is a liquid composition comprising said biological material having polyester degrading activity, a polysaccharide carrier and water, or - a masterbatch comprising said polyester-degrading biological material and a carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C in a form suitable for uniformly dispersing said biological material in said plastic article.

[0099] Preferably, the mixing step (a) is carried out at a temperature at which the polyester is in a partially or completely molten state and / or in the extruder.

[0100] The polyester, biological material and carrier, as well as their ratios in the plastic article are defined above and in the examples, and one skilled in the art can adjust the ratio of each component used in the above method to obtain the final ratio.

[0101] liquid composition In a first embodiment, the biological material is provided in the form of a liquid composition.

[0102] Preferably, the liquid composition comprises, based on the total weight of the composition: - 0.01% to 35% by weight of biological material, - 15% to 95% by weight of an aqueous solvent; - 3% to 80% by weight of a polysaccharide carrier; Includes.

[0103] In particular, the biological material retains polyester degradation activity in the plastic composition and / or the final plastic article.

[0104] The liquid composition is suitable for co-extrusion with polymers.Preferably, the composition is suitable for co-extrusion with synthetic polymers, such as polyolefins, aliphatic or aromatic polyesters, polyamides, polyurethanes and polyvinyl chloride, or natural polymers, such as lignin and polysaccharides, such as cellulose, hemicellulose, starch and their derivatives.In a preferred embodiment, the composition is suitable for co-extrusion with polymers having a low melting temperature, i.e. melting point (Tm), i.e. having a Tm of less than 140°C.

[0105] In a preferred embodiment, the aqueous solvent is water, in such an embodiment, the composition comprises 15%-95% water, and 5%-85% other components, such as at least 0.01%-35% biological material and 3%-80% carrier, based on the total weight of the composition.

[0106] In certain embodiments, the liquid composition comprises, based on the total weight of the composition, - 0.3% to 30% by weight of biological material, - 19% to 85% by weight of an aqueous solvent; - 4% to 80% by weight of a polysaccharide carrier; Includes.

[0107] In a preferred embodiment, the liquid composition comprises less than 35% by weight of biological material. In another specific embodiment, the composition comprises less than 30% by weight of biological material. In another specific embodiment, the composition comprises less than 20% by weight of biological material.

[0108] In a particular preferred embodiment, the liquid composition comprises less than 80% by weight, preferably less than 75% by weight, less than 70% by weight, and even more preferably less than 60% by weight of aqueous solvent, based on the total weight of the composition. In another preferred embodiment, the composition comprises more than 20% by weight, preferably more than 30% by weight and less than 80% by weight of aqueous solvent, based on the total weight of the composition. In another particular embodiment, the composition comprises 20% to 80% by weight, preferably 30% to 75% by weight, and more preferably 40% to 60% by weight of aqueous solvent. In another particular embodiment, the composition comprises about 50% aqueous solvent. In another particular embodiment, the composition comprises about 40% aqueous solvent. In a preferred embodiment, the aqueous solvent is water. In a preferred embodiment, the liquid composition comprises less than 75% by weight, preferably less than 70% by weight, and more preferably less than 60% by weight of water, based on the total weight of the composition. In another preferred embodiment, the composition comprises more than 20% by weight, preferably more than 30% by weight and less than 80% by weight of water, based on the total weight of the composition. In another particular embodiment, the composition comprises 20% to 80% by weight, preferably 30% to 75% by weight, more preferably 40% to 60% by weight of water. In another particular embodiment, the composition comprises about 50% water. In another particular embodiment, the composition comprises about 40% water.

[0109] In certain preferred embodiments, the liquid composition comprises more than 5% by weight of the polysaccharide carrier, preferably more than 10% by weight, and even more preferably more than 15% by weight.

[0110] Thus, in a preferred embodiment, the composition comprises, based on the total weight of the composition: - 0.3% to 30% by weight of biological material, - 19% to 60% by weight of an aqueous solvent; - 15% to 70% by weight of a polysaccharide carrier; Includes.

[0111] In another preferred embodiment, the composition comprises less than 70% by weight, preferably less than 60% by weight, of the carrier. In a specific embodiment, the composition comprises 5% to 70%, preferably 10% to 60% of the carrier. In another specific embodiment, the composition comprises 10% to 50% of the carrier.

[0112] In another particular embodiment, the composition comprises, based on the total weight of the composition: - 0.01-35% biological material; - 30-75% water, - 10~69.99% carrier and Includes.

[0113] In another particular embodiment, the composition comprises, based on the total weight of the composition: - 0.01-35% biological material; - 30-60% water, - 20-45% carrier Includes.

[0114] In another particular embodiment, the composition comprises, based on the total weight of the composition: - 0.01-35% biological material; - 40-60% water, - 20-45% carrier Includes.

[0115] In another specific embodiment, the composition comprises about 50% water, 0.01%-35% biological material, and 20%-50% carrier.

[0116] In another specific embodiment, the composition comprises about 40% water, 0.01%-35% biological material, and 20%-60% carrier.

[0117] In certain embodiments, the weight ratio of polysaccharide carrier to aqueous solvent is less than 4.

[0118] In certain embodiments, the amount of polysaccharide carrier in the composition is between 4% and 100% of the maximum solubility of the carrier in the aqueous solvent, ie, between 4% and 100% of the saturation concentration of the carrier in the aqueous solvent.

[0119] Alternatively or additionally, the amount of polysaccharide carrier in the composition is from 4% to 100% of the maximum solubility of the carrier in the composition, ie, from 4% to 100% of the saturation concentration of the carrier in the composition.

[0120] According to the invention, the presence of a polysaccharide carrier in the composition makes it possible to protect and stabilize the biological material not only in the composition but also during thermal treatments such as extrusion processes in which the composition is partially or completely introduced into a molten polymer.

[0121] In certain embodiments, the carrier is in solid form at ambient temperature. Advantageously, the carrier is soluble in an aqueous solvent such as water at ambient temperature. Preferably, the carrier is soluble in the liquid composition at least at ambient temperature. Alternatively or additionally, the carrier is soluble in the liquid composition at a temperature of about 100°C.

[0122] In certain embodiments, the carrier is a starch derivative. Preferably, the carrier is maltodextrin. In such certain embodiments, the weight ratio of maltodextrin / aqueous solvent is preferably 3-4. In certain embodiments, the amount of maltodextrin in the composition is 5-100%, preferably 26-100%, more preferably 39-100% of its maximum solubility in the composition. Thus, the composition comprises more than 4% by weight, preferably more than 20% by weight, preferably more than 30% by weight, of maltodextrin, based on the total weight of the composition.

[0123] In certain embodiments, the carrier is naturally occurring GumPreferably, the carrier is selected from gum arabic, guar gum, gum tragacanth, gum karaya, more preferably the carrier is gum arabic. In a particular embodiment, the weight ratio of gum arabic / aqueous solvent is 0.1-1, preferably 0.3-0.8, more preferably 0.35-0.6, even more preferably 0.4-0.5. In another preferred embodiment, the weight ratio of gum arabic / aqueous solvent is greater than 0.8, preferably 0.8-1. In particular, the amount of gum arabic in the composition is 6%-100% of its maximum solubility in the composition, preferably 40%-100% of its maximum solubility, preferably 60%-100% of its maximum solubility. In another particular embodiment, the composition comprises more than 4% by weight of gum arabic, preferably more than 10%, more preferably more than 15%, even more preferably more than 20%. In another preferred embodiment, the composition comprises less than 70% by weight of gum arabic, preferably less than 60% by weight. In a particular embodiment, the composition comprises 5% to 70%, preferably 10% to 60% gum arabic, hi another particular embodiment, the composition comprises 10% to 50% gum arabic.

[0124] In a particular embodiment, the carrier is a marine extract. Preferably, the carrier is selected from carrageenan or alginate.

[0125] In another particular embodiment, the carrier is a microbial polysaccharide. Preferably, the carrier is xanthan.

[0126] In another particular embodiment, the carrier is an animal polysaccharide. Preferably, the carrier is chitosan.

[0127] In certain embodiments, the liquid composition comprises a starch derivative, natural Gum, marine extracts, microorganisms and animal polysaccharides. In another particular embodiment, the ratio of carrier / biological material is 0.8-1.2, preferably about 1. In another particular embodiment, the ratio of carrier / biological material is more than 1, preferably more than 2. According to the present invention, the liquid composition may further comprise sugars, proteins, lipids, organic acids, salts and vitamins derived from the culture supernatant of the polyester-degrading microorganism used as the biological material in the composition. Such supernatant may be pre-treated (e.g. mechanically or physically or chemically) to increase the concentration of enzymes and / or to remove other components such as DNA or cell debris.

[0128] In a particular embodiment, the composition may further comprise a polyol, such as glycerol, sorbitol or propylene glycol. This is particularly true when the composition of the invention is produced using commercially available biological substances, preferably commercially available enzymes, prepared in a stabilizing solution containing a polyol. According to a particular embodiment, the composition comprises up to 10% by weight, preferably up to 5% by weight, of polyol based on the total weight of the composition. According to another particular embodiment, the composition comprises 10% to 20% by weight of polyol based on the total weight of the composition.

[0129] According to certain embodiments, the liquid composition may comprise insoluble components with a particle size of less than 20 μm.

[0130] Alternatively or additionally, the composition further comprises an inorganic component, such as a calcium component, which is known to enhance the thermal stability of some biological materials, such as calcium carbonate, calcium chloride or other calcium minerals.

[0131] Advantageously, the liquid composition of the present invention is stable, i.e. chemically and biologically stable. In the present invention, "chemically stable" refers to a composition in which the biological material does not show significant loss of activity at room temperature in the dark for a given period of time. More specifically, "chemically stable" refers to a composition in which the loss of degradation activity of the biological material is less than 50%, preferably less than 25%, more preferably less than 10%, for at least 30 days, preferably at least 90 days, more preferably at least 1 year, compared to the degradation activity of the biological material before being introduced into the composition. According to the present invention, the composition of the present invention is chemically stable at 4°C for at least 90 days. In particular, the loss of degradation activity of the biological material in the composition of the present invention is less than 10% for at least 90 days, compared to the degradation activity of the biological material before being introduced into the composition. In the present invention, the term "biologically stable" refers to a composition in which the growth of bacteria, yeast or fungi is not observed for at least 30 days, preferably at least 90 days, more preferably at least 1 year, for at least 30 days, preferably at least 90 days, more preferably at least 1 year, in the dark at room temperature. In particular, the composition further comprises antifungal and / or antibacterial components, such as sorbic acid and / or its salts, benzoic acid and its salts, sulfurous anhydride or sulfite, nitrate or nitrite, propionic acid, butyric acid, natamycin, parabens, acetic acid, citric acid, boric acid, plant extracts.

[0132] In another particular embodiment, the composition comprises, based on the total weight of the composition: - 0.01-35% PLA degrading enzyme; - 30-75% water, - 10 to 69.99% gum arabic Includes.

[0133] In another particular embodiment, the composition comprises, based on the total weight of the composition: - 0.01-35% PLA degrading enzyme; - 30-60% water, - 20-45% gum arabic Includes.

[0134] In another particular embodiment, the composition comprises, based on the total weight of the composition: - 0.01-35% PLA degrading enzyme; - 40-60% water, - 20-45% gum arabic Includes.

[0135] In another particular embodiment, the composition comprises about 50% water, 0.01%-35% PLA degrading enzyme, and 20%-50% gum arabic.

[0136] In another particular embodiment, the composition comprises about 40% water, 0.01%-35% PLA degrading enzyme, and 20%-60% gum arabic.

[0137] All the above compositions optionally contain 0%-20%, preferably 0%-5%, of other ingredients, preferably selected from proteins, salts, polyols. Furthermore, the PLA degrading enzyme of such compositions is preferably selected from proteases.

[0138] In certain embodiments, the liquid composition of the present invention comprises, based on the total weight of the composition, - 20% to 80% by weight of water, preferably 40% to 60% by weight of water, - 0.01% to 30% by weight of a PLA degrading enzyme, preferably 5% to 30% by weight of a protease; - 10% to 50% by weight, preferably 15% to 35% by weight, of gum arabic; Includes.

[0139] In certain embodiments, the composition of the present invention comprises, based on the total weight of the composition: - 20% to 80% by weight of water, preferably 40% to 60% by weight of water, - 0.01% to 30% by weight of a PLA degrading enzyme, preferably 5% to 30% by weight of a protease; - 10% to 50% by weight, preferably 15% to 35% by weight, of gum arabic, - 0% to 20% by weight of other ingredients, preferably selected from proteins, salts, polyols Includes.

[0140] In certain embodiments, the composition of the present invention comprises, based on the total weight of the composition: - 20% to 80% by weight of water, preferably 40% to 60% by weight of water, - 0.01% to 30% by weight of a PLA degrading enzyme, preferably 5% to 30% by weight of a protease; - 10% to 50% by weight, preferably 15% to 40% by weight, of maltodextrin; Includes.

[0141] In certain embodiments, the composition of the present invention comprises, based on the total weight of the composition: - 20% to 80% by weight of water, preferably 40% to 60% by weight of water, - 0.01% to 30% by weight of a PLA degrading enzyme, preferably 5% to 20% by weight of a protease; - 10% to 50% by weight, preferably 15% to 40% by weight, of maltodextrin; - 0% to 20% by weight of other ingredients, preferably selected from proteins, salts, polyols Includes.

[0142] Advantageously, the liquid composition is in liquid form at least at ambient temperature. Preferably, the liquid composition is in liquid form at the temperature at which it is introduced into the polymer in a partially or completely molten state.

[0143] Advantageously, in all the above compositions, the amounts of carrier and biological material are expressed as dry matter, ie after complete dehydration or evaporation or removal of water.

[0144] Masterbatch In a particular embodiment, the liquid composition of biological material is introduced into a first carrier polymer, such as PCL, PBSA, PBAT, having a low melting point (less than 140°C, preferably less than 120°C) and / or a low glass transition temperature (less than 70°C), to prepare a masterbatch. The resulting masterbatch is then added to a second polyester, particularly PLA, having a high melting point. For example, the liquid composition is added to PCL, which has been heated to about 70°C so that it is in a partially molten state. The mixture is then added directly to PLA, which has been heated to about 150°C so that it is in a partially molten state. Alternatively, the mixture may be cooled and, optionally, conditioned, and then added to the second polyester while at least partially molten.

[0145] Masterbatches in molten or solid form are also part of this invention.

[0146] Thus, the present invention provides a masterbatch comprising a biological material having polyester degrading activity and a carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C.

[0147] The biological material and the carrier polymer are defined above and in the Examples, and all definitions and strictures regarding the nature, composition and properties of said components defined in relation to the plastic article also apply to the definition of the masterbatch.

[0148] The masterbatch in particular comprises 50% to 95% by weight of carrier polymer, preferably 70% to 90% by weight of carrier polymer, based on the total weight of the masterbatch.

[0149] The masterbatch advantageously comprises between 5% and 50% by weight of the biological material composition, between 10% and 30% by weight of the biological material composition, based on the total weight of the masterbatch.

[0150] Advantageously, the masterbatch is prepared using a liquid composition of biological material comprising a polysaccharide carrier as defined above.

[0151] The masterbatch of the present invention therefore also comprises a polysaccharide carrier as defined above. In particular, the masterbatch comprises 1% to 30%, preferably 1% to 15%, of a polysaccharide carrier, based on the total weight of the masterbatch.

[0152] Advantageously, the residence time of the liquid composition, and therefore the biological material, in the carrier polymer at temperatures above 100° C. is as short as possible, preferably between 5 seconds and 10 minutes, more preferably less than 5 minutes, 3 minutes, 2 minutes.

[0153] The following is a description of the method of using the masterbatch to prepare the above-mentioned plastic article, with or without the step in which the masterbatch is in a solid state, which is prepared for further use in the method of manufacturing the article according to the present invention. The carrier polymer may also be identified as the "first polymer". In the description of the masterbatch, its preparation and use, the definition, accuracy and properties of the carrier polymer are the same as those of the first polymer.

[0154] For example, the method comprises: a) a masterbatch comprising a polyester degraded biological material and a carrier polymer, (i) heating the carrier polymer; and (ii) introducing 5% to 50% by weight of the biological material, based on the total weight of the masterbatch, during heating of the carrier polymer; and (b) incorporating the masterbatch into a polyester matrix during the manufacture of a plastic article; Including, wherein step (a) is carried out at a temperature at which the carrier polymer is partially or completely molten and the biological material degrades the polyester of the polyester-based matrix and is introduced during step (ii) in the form of a liquid composition as defined above, and wherein step b) is carried out at a temperature at which both the first polymer and the polyester of the polyester-based matrix are partially or completely molten.

[0155] Thus, step (a) of preparing the masterbatch may be carried out at a temperature of 40° C. or more, in particular 45° C., 55° C., 60° C., 70° C., 80° C., 90° C., 100° C. or more, or more than 150° C., depending on the nature of the first polymer. Typically, this temperature does not exceed 300° C. More particularly, the temperature does not exceed 250° C. Even more particularly, the temperature does not exceed 200° C. Step (a) is carried out using a carrier polymer with a low melting point, i.e. a melting point below 140° C. and / or a low glass transition temperature (below 70° C.). For example, step (a) is carried out using PCL, PBAT or PBSA. The temperature of the mixing step can be adapted by the skilled person depending on the type of polymer and / or biological material used to prepare the masterbatch. In particular, the temperature is selected depending on the melting point, i.e. the melting temperature, of the first polymer. In a particular embodiment, step (a) is carried out at the melting point of the first polymer. In that case, the polymer is in a partially or completely molten state. In another embodiment, step (a) is carried out at a temperature above the glass transition temperature of the polymer, in particular at a temperature between the glass transition temperature (Tg) and the melting temperature of the polymer. In another particular embodiment, the mixing step (a) is carried out at a temperature above the melting temperature of the polymer.

[0156] According to the invention, the carrier polymer is heated at a temperature below 140° C. and the biological material is introduced into the first polymer during said heating step. More generally, the masterbatch preparation step (step a) is carried out at a temperature at which the first polymer is in a partially or completely molten state, so that the biological material is embedded in the first polymer during extrusion. Preferably, step a) is carried out by extrusion.

[0157] In a preferred embodiment, a masterbatch is prepared by (i) extruding a carrier polymer having a melting temperature below 140° C., and (ii) introducing a biological material during the extrusion of the first polymer, followed by introducing the masterbatch into a polyester matrix to prepare a plastic article.

[0158] In a particular embodiment, the carrier polymer is a polyester, preferably selected from polycaprolactone (PCL), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), polyhydroxyalkanoate (PHA), polylactic acid (PLA), or a copolymer. In another particular embodiment, the first polymer is a natural polymer, preferably selected from starch. In another particular embodiment, the masterbatch comprises a "universal" polymer, i.e., a polymer that is compatible with a wide range of polymers, such as copolymers (e.g., ethylene vinyl acetate copolymer, EVA).

[0159] The masterbatch comprises a first polymer having a melting temperature of less than 140° C. and / or a glass transition temperature of less than 70° C. Preferably, the first polymer of the masterbatch has a melting temperature of less than 120° C. and / or a glass transition temperature of less than 30° C. For example, such a first polymer is selected from the group consisting of PCL, PBAT, PLA and EVA. Preferably, such a first polymer is selected from the group consisting of PCL, PBAT and PLA. An advantage of such an embodiment is that it reduces heating of the biological material during the masterbatch manufacturing process.

[0160] The masterbatch comprises 5% to 50% by weight of the biological material based on the total weight of the masterbatch, the biological material being provided in the form of the liquid composition described above. Preferably, the biological material represents 10% to 40% by weight, more preferably 10% to 30% by weight, based on the total weight of the masterbatch. In certain embodiments, the masterbatch comprises about 20% by weight of the biological material composition. In certain embodiments, the polyester-degrading biological material is capable of degrading the first polymer. Alternatively or additionally, the polyester-degrading organism is capable of degrading at least one polyester of a final plastic article incorporating the masterbatch.

[0161] The masterbatch may further comprise one or several additional compounds. In particular, the masterbatch may further comprise one or more additives. Generally speaking, additives are used to improve certain properties of the final product. For example, the additives may be selected from the group consisting of plasticizers, colorants, processing aids, rheological agents, antistatic agents, anti-UV agents, toughening agents, impact modifiers, compatibilizers, slip agents, flame retardants, antioxidants, pro-oxidants, light stabilizers, oxygen scavengers, adhesives, products, excipients, slip agents, but are not limited thereto. Advantageously, the masterbatch comprises less than 20% by weight of additives, preferably less than 10% by weight, typically 0.1-10% by weight of additives, based on the total weight of said masterbatch. Preferably, the masterbatch comprises at least one additive selected from plasticizers, slip agents and light stabilizers. In particular, the masterbatch may further comprise at least one filler. The filler may be selected from any conventional filler used in the plastics industry. The type and exact amount of filler can be adapted by the skilled artisan depending on the type of masterbatch composition. Advantageously, the masterbatch comprises at least one filler selected from acid-resistant fillers selected from calcium carbonate, talc or silica.

[0162] In certain embodiments, the masterbatch composition comprises, based on the total weight of the masterbatch, - 50-95% by weight of a carrier polymer; - 5 to 50% by weight of polyester decomposed biological material; optionally - at least one additive; Includes.

[0163] In another particular embodiment, the masterbatch comprises, based on the total weight of the masterbatch, - 70-90% by weight of a carrier polymer; - 10 to 30% by weight of polyester decomposed biological material; optionally - at least one additive; Includes.

[0164] In certain embodiments, the masterbatch is produced by a process called "compounding", typically an extrusion granulation process in which a first polymer is melted and mixed with a biological material. Compounding combines mixing and blending techniques during a heating process to ensure uniformity, homogeneity and dispersion of the masterbatch. Compounding is a technique known to those skilled in the art. Such a compounding process may be carried out using extruders such as single screw extruders, multi-screw extruders of co-rotating or counter-rotating design, dispersion kneaders, reciprocating single screw extruders (co-kneaders), etc.

[0165] More generally, step (a) of preparing the masterbatch can be carried out using an extruder, in which the first polymer is heated, melted and mixed with the biological material. The first polymer may be introduced into the extruder in the form of a powder or granules, preferably in the form of granules.

[0166] In a preferred embodiment, the extruder used in the masterbatch preparation step (a) is a multi-screw extruder, preferably a twin-screw extruder, more preferably a co-rotating twin-screw extruder. In a particular embodiment, the extruder further comprises a static mixer after the screw. In another embodiment, the extruder is used with a die with holes, preferably a die with at least two holes. Those skilled in the art will easily adapt the characteristics of the die (such as the number and size of the holes) to the intended pressure, output or masterbatch.

[0167] In a preferred embodiment, the residence time of the mixture of the first polymer and drug in the extruder is between 5 seconds and 3 minutes, preferably less than 2 minutes. If the masterbatch contains a polymer with a melting temperature less than 120° C., the residence time of the mixture in the extruder is between 5 seconds and 10 minutes, preferably less than 5 minutes.

[0168] One skilled in the art will readily adapt the extruder characteristics (e.g., screw length and diameter, screw profile, degassing zones, etc.) and residence time to the type of first polymer, biological material, and masterbatch contemplated.

[0169] As disclosed above, the biological material is preferably introduced into the extruder in the form of a liquid composition as described above.

[0170] In particular, such extruders may include a main hopper and several successive heating zones, the temperatures of which may be independently controlled and adjusted, and additional ingredients may be added at different points during the process. Vacuum and natural degassing zones are required during extrusion to remove volatile products such as water.

[0171] The liquid composition of biological material is introduced by pump. In a particular embodiment, the biological material is introduced at a later stage of the mixing process (i.e., the last heating zone), more specifically when the first polymer is in a partially or completely molten state. Thus, exposure to high temperatures is reduced. Preferably, the residence time of the composition in the extruder is less than or equal to half the residence time of the first polymer. In another particular embodiment, the biological material is introduced into the extruder before the polymer. Thus, contact between the composition and the polymer is increased.

[0172] According to the present invention, after step (a) of preparing the masterbatch, the masterbatch may be adjusted to any suitable solid form. In this regard, in a preferred embodiment, the masterbatch is formed into a rod through a die. The rod is then cooled and then chopped into masterbatch granules and / or lozenges, and optionally dried. An underwater pelletizer may be used. In a further embodiment, the masterbatch granules may be crushed or pulverized to produce the masterbatch powder. The powder may then be subjected to an extrusion granulation process, preferably in an extruder, so that the mixture is in a partially or completely molten state before step (b).

[0173] According to the method of the present invention, the masterbatch is introduced into the polyester matrix during step (b) to produce the plastic article of the present invention. The step of introducing the masterbatch into the polyester matrix is ​​carried out at a temperature at which the first polymer and at least one polyester of the polyester matrix are in a partially or completely molten state. When the masterbatch and the polyester matrix of step (a) are in granular form, it is possible to subject the granules to a step of dry mixing before step (b) of introducing the masterbatch into the polyester matrix.

[0174] Preferably, the polyester matrix comprises at least one polyester chosen from copolymers of lactic acid and / or succinic acid and / or terephthalic acid or mixtures thereof.

[0175] Advantageously, the polyester matrix comprises at least one polyester chosen from polylactic acid (PLA), polyglycolic acid (PGA), polyhydroxyalkanoate (PHA), polycaprolactone (PCL), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), and derivatives or blends / mixtures thereof. In a preferred embodiment, the polyester matrix comprises at least one polyester chosen from PLA and / or PCL and / or PBAT, more preferably at least PLA.

[0176] Those skilled in the art can select the polyester of the polyester-based matrix depending on the properties of the final plastic article.

[0177] According to the invention, the polyester-based matrix may further comprise at least one natural polymer and / or at least one filler and / or at least one additive.

[0178] The natural polymer may be selected from the group of lignin, polysaccharides such as cellulose or hemicellulose, starch, chitin, chitosan, and derivatives thereof or blends / mixtures thereof. In certain embodiments, the natural polymer is plasticized (e.g., with water or a plasticizer such as glycerol) before being used to prepare the masterbatch composition. Such a plasticization step modifies the chemical structure of the natural polymer, making it usable in the plastics manufacturing process.

[0179] The filler can be selected from any conventional filler used in the plastics industry. The type and exact amount of filler can be adapted by those skilled in the art depending on the type of masterbatch composition and following the guidance provided in this application. Advantageously, the plastic article comprises at least one filler selected from calcium carbonate, talc or silica.

[0180] It is an object of the present invention to provide a method for mixing a polyester matrix with a masterbatch containing a large amount of biological material to achieve a plastic article with a precise loading and uniform distribution of the biological material.

[0181] According to the invention, after the mixing step (a) and optionally preparing the mixture in a suitable solid form, (b) the produced plastic composition is molded into a plastic article.

[0182] In a particular embodiment, step (b) is carried out using a polyester with a high melting point, i.e., a melting point above 140° C. For example, step (b) is carried out using PLA.

[0183] Advantageously, step (b) is carried out at a temperature at which the polyester and the first polymer of the polyester matrix are in a partially or completely molten state. For example, step (b) may be carried out at a temperature of 40° C. or more, in particular 45° C., 55° C., 60° C., 70° C., 80° C., 90° C., 100° C. or more, or more than 150° C., depending on the nature of the polymer. Typically, this temperature does not exceed 300° C. More particularly, the temperature does not exceed 250° C. Even more particularly, the temperature does not exceed 200° C. The temperature of step (b) can be adapted by the skilled person depending on the type of masterbatch and polyester matrix and / or the nature of the intended plastic article. In particular, the temperature is selected depending on the melting point, i.e. the melting temperature, of the polyester and the first polymer of the polyester matrix.

[0184] In a particular embodiment, step (b) is carried out at the melting temperature of the polyester of the polyester matrix, whereby the polyester is in a partially or completely molten state. In another embodiment, step (b) is carried out at a temperature between the glass transition temperature (Tg) and the melting point of the polyester. In another particular embodiment, step (b) is carried out at a temperature above the melting point of the polyester.

[0185] Typically, said step (b) may be carried out by extrusion, extrusion compounding, extrusion blow molding, blown film extrusion, cast film extrusion, calendering and thermoforming, injection molding, compression molding, extrusion swelling, rotational molding, ironing, coating, layering, expansion, pultrusion, compression granulation, or 3D printing. Such operations are well known to those skilled in the art who easily adapt the process conditions (e.g., temperature, residence time, etc.) according to the nature of the intended plastic article. As an example, blown film extrusion is particularly suitable for the production of plastic films. As another example, cast film extrusion is particularly suitable for the production of plastic sheets, while injection molding, thermoforming, blow molding, rotational molding, or 3D printing are particularly suitable for the production of rigid plastic articles.

[0186] In a particular embodiment, step (b) is carried out with a solid masterbatch in the form of a powder or granules, preferably in the form of a granule.

[0187] In certain embodiments, 0.5 to 30% by weight of the masterbatch is added to the polyester matrix, preferably less than 20% by weight, more preferably less than 15% by weight, and even more preferably less than 10% by weight, based on the total weight of the plastic article. In certain embodiments, about 5% by weight of the masterbatch is introduced into the polyester matrix.

[0188] In another particular embodiment, 1% to 5% by weight of the masterbatch is incorporated into and / or mixed with 95% to 99% by weight of a partially or completely molten polyester matrix.

[0189] In another particular embodiment, the present invention relates to a method for preparing a plastic article comprising at least PLA, a) a masterbatch comprising PLA degraded biological material and PCL, (i) heating the PCL; and (ii) introducing 5 wt% to 50 wt% of the PLA-degrading biological material based on the total weight of the masterbatch during heating of the PCL; and (b) introducing the masterbatch into a PLA-based matrix during the manufacture of a plastic article; Including, wherein step (a) is carried out at a temperature at which the PCL is partially or completely molten, preferably above 65°C, more preferably above about 70°C, and the biological material is introduced during step (ii) in the form of a liquid composition, and wherein step b) is carried out at a temperature at which both the PCL and the PLA are partially or completely molten, preferably above 120°C, more preferably above about 155°C.

[0190] direct manufacturing In another embodiment, the liquid composition of the biological material is directly introduced into the polymer that makes up the plastic article.

[0191] The object of the present invention is also to provide a method for preparing said plastic article, comprising the steps of: (a) mixing with at least said polyester a biological material having a polyester-degrading activity of less than 11% by weight, in particular between 0.1% and 10% by weight, - (b) forming the mixture of step (a) into a plastic article. wherein in step (a) the biological material is mixed in the form of a liquid composition comprising a polysaccharide carrier.

[0192] In certain embodiments, the method further comprises the step of mixing at least one additive and / or at least one second polyester and / or natural polymer with the polyester and biological material prior to step (b). Alternatively, such additives and / or polyester and / or natural polymer can be mixed with the polyester and biological material in step (a).

[0193] In a particular embodiment, the polyester used in step (a) is in granular form. In another embodiment, the polyester is in powder form. To this end, before the mixing step (a), the polyester can be mechanically pretreated to be in powder form. In particular, the polyester can be ground.

[0194] The mixing step (a) is carried out at a temperature at which the polyester is in a partially or completely molten state. Thus, the mixing step (a) may be carried out at a temperature of 40° C. or more, in particular 45° C., 55° C., 60° C., 70° C., 80° C., 90° C., 100° C. or more, or more than 150° C., depending on the nature of the polyester. Typically, this temperature does not exceed 300° C. More particularly, the temperature does not exceed 250° C. The temperature of the mixing step can be adapted by the skilled person depending on the type of polyester and / or biological material used for the manufacture of the plastic article. In particular, the temperature is selected depending on the melting point, i.e. the melting temperature, of the polyester. In a particular embodiment, the mixing step (a) is carried out at the melting point of the polyester of the plastic article. The polyester is then in a partially or completely molten state. In another embodiment, the mixing step (a) is carried out at a temperature higher than the glass transition temperature of the polyester, in particular at a temperature between the glass transition temperature (Tg) and the melting temperature of the polyester. In another particular embodiment, the mixing step (a) is carried out at a temperature above the melting temperature of the polyester.

[0195] In certain embodiments, the plastic composition may be produced from step a) by a process called "compounding", typically an extrusion-granulation process in which the polyester is melted and mixed with the biological material. Compounding combines mixing and blending techniques during the heating process to ensure uniformity, homogeneity and dispersion of the final compound. Compounding is a technique known to those skilled in the art. Such compounding processes may be carried out using extruders such as single screw extruders, multi-screw extruders of co-rotating or counter-rotating design, dispersion kneaders, reciprocating single screw extruders (co-kneaders), etc.

[0196] Preferably, the mixing step (a) may be carried out using an extruder, in which the polyester is heated, melted and mixed with the biological material. The polyester may be introduced into the extruder in the form of a powder or granules, preferably in the form of granules.

[0197] According to a particular embodiment, the mixing step (a) comprises a first step of introducing the biological material into a first polymer having a low melting point (less than 140°C, preferably less than 120°C), such as PCL, PBSA, PBAT, etc.; and then a second step of adding a polyester matrix comprising a second polyester having a high melting point, such as PLA, to the mixture obtained in the first step. For example, the liquid composition is added to PCL heated to about 70°C so that it is in a partially molten state. Then, PLA heated to about 150°C and in a partially molten state is added directly to the mixture.

[0198] In a preferred embodiment, the extruder used in step a) for the preparation of the plastic composition is a multi-screw extruder, preferably a twin-screw extruder, more preferably a co-rotating twin-screw extruder. In a particular embodiment, the extruder further comprises a static mixer after the screws. In another embodiment, the extruder is used with a die with holes.

[0199] In a preferred embodiment, the residence time of the mixture in the extruder is between 5 seconds and 3 minutes, preferably less than 2 minutes. If the plastic composition comprises a polyester having a melting temperature less than 120° C., the residence time of the mixture in the extruder is preferably less than 5 minutes.

[0200] One skilled in the art will readily adapt the extruder characteristics (eg, screw length and diameter, screw profile, venting zones, etc.) and residence time to the type of polyester, biological material, and plastic composition intended.

[0201] As disclosed above, the biological material is preferably introduced into the extruder in the form of a liquid composition as described above.

[0202] In particular, such extruders may include a main hopper and several successive heating zones, the temperatures of which may be independently controlled and adjusted, and additional ingredients may be added at different points during the process. Vacuum and natural degassing zones are required during extrusion to remove volatile products such as water.

[0203] The biological material in liquid form is introduced by pump. In a particular embodiment, the biological material is introduced at a later stage of the mixing process (i.e., the last heating zone), more specifically when the polyester is in a partially or completely molten state. Thus, exposure to high temperatures is reduced. Preferably, the residence time of the biological material in the extruder is half or less than that of the polyester. In another particular embodiment, the liquid composition is introduced into the extruder before the polyester. Thus, contact between the composition and the polyester is increased.

[0204] According to a particular embodiment, the mixing step (a) is carried out using two extruders, namely a main extruder and a second extruder connected to the main extruder, in which the biological material is mixed with a first polyester having a melting temperature below 140° C. and introduced into a zone in the main extruder where the polyester matrix is ​​already in a partially or completely molten state. Such a polyester matrix comprises at least a natural polymer selected from a polyester that is degraded by the biological material, and finally a plasticized starch. According to a particular embodiment, the main extruder is selected from a single screw extruder or a multi-screw extruder and the second extruder is selected from a single screw extruder, a multi-screw extruder or a side feeder.

[0205] According to the present invention, after the mixing step (a), the mixture may be adjusted to any suitable solid form. In a preferred embodiment in this regard, the mixture of step (a) is shaped into a rod through a die. The rod is then cooled, optionally dried, and chopped into granules of the plastic composition. In a further embodiment, the granules of the plastic composition may be crushed or pulverized to produce a powder of the plastic composition.

[0206] According to the invention, after the mixing step (a) and optionally preparing the mixture in a suitable solid form, (b) the produced plastic composition is molded into a plastic article.

[0207] Advantageously, step (b) is carried out at a temperature at which the polyester of the plastic composition is in a partially or completely molten state. For example, step (b) may be carried out at a temperature of 40° C. or more, in particular 45° C., 55° C., 60° C., 70° C., 80° C., 90° C., 100° C. or more, or even more than 150° C., depending on the nature of the polyester in the plastic composition. Typically, this temperature does not exceed 300° C. More particularly, the temperature does not exceed 250° C. The temperature of step (b) can be adapted by the skilled person depending on the plastic composition and the type of polyester it contains and / or the nature of the intended plastic article. In particular, the temperature is selected depending on the melting point, i.e. the melting temperature, of the polyester of the plastic composition produced in step (a).

[0208] In a particular embodiment, step (b) is carried out at the melting temperature of the polyester of the plastic composition, whereby the polyester is in a partially or completely molten state. In another embodiment, step (b) is carried out at a temperature between the glass transition temperature (Tg) and the melting point of the polyester. In another particular embodiment, step (b) is carried out at a temperature above the melting point of the polyester.

[0209] Typically, said step (b) may be carried out by extrusion, extrusion compounding, extrusion blow molding, blown film extrusion, cast film extrusion, calendering and thermoforming, injection molding, compression molding, extrusion swelling, rotational molding, ironing, coating, layering, expansion, pultrusion, compression granulation, or 3D printing. Such operations are well known to those skilled in the art who easily adapt the process conditions (e.g., temperature, residence time, etc.) according to the nature of the intended plastic article. As an example, blown film extrusion is particularly suitable for the production of plastic films. As another example, cast film extrusion is particularly suitable for the production of plastic sheets, while injection molding, thermoforming, blow molding, rotational molding, or 3D printing are particularly suitable for the production of rigid plastic articles.

[0210] In a preferred embodiment, step (b) is carried out with a solid plastic composition in the form of a powder or granules, preferably in the form of granules.

[0211] The plastic article comprises a biological material in the form of a liquid composition in an amount of 0.1% to 10% by weight based on the total weight of the plastic article. Preferably, the liquid composition of biological material represents 0.1% to 5%, more preferably 0.1% to 3% of the plastic article.

[0212] According to another embodiment, the biological material in the form of a liquid composition is directly introduced in step (b) of molding the plastic article.

[0213] In a particular embodiment, the present invention relates to a method for preparing a plastic composition comprising the steps of: (a) mixing a protease having a PLA degrading activity of 0.1% by weight to 10% by weight based on the total weight of the plastic composition with PLA; - step (b) of forming said mixture of step (a) into a plastic article. wherein the mixing step (a) is preferably carried out at a temperature of 150-180° C. and / or in an extruder, preferably a twin screw extruder, more preferably a co-rotating twin screw extruder.

[0214] A further object of the present invention is to provide a method for the production of a plastic article containing a biological material comprising successive steps of introducing the liquid composition of the present invention into a first polymer to obtain a mixture, and introducing said mixture into a second polymer different from the first polymer, the first polymer having a melting point below 140°C and the second polymer having a melting point above 140°C.

[0215] More generally, the plastic articles may be manufactured by any technique known to those skilled in the art.

[0216] It is yet another object of the present invention to provide a method for improving the distribution uniformity of a biological material in a plastic article comprising at least one polyester and a polyester-degraded biological material, the method comprising introducing the biological material in the form of a liquid composition in the manufacturing process of the plastic. EXAMPLES

[0217] Example 1 - Use of a liquid composition containing biological material to produce a film of the invention containing PCL and PLA, and evaluation of the biodegradability of the film of the invention 1.1-Preparation of liquid compositions containing biological substances Various liquid compositions were prepared using Savinase® 16L (Novozymes), a commercial protease sold in liquid form (containing more than 50% by weight of polyol based on the total weight of the liquid composition and water). Such enzymes are known for their ability to degrade polylactide (Degradation of Polylactide by commercial proteases; Y. Oda, A. Yonetsu, T. Urakami and K. Tonomura; 2000).

[0218] Liquid composition A (LC-A) was obtained by ultrafiltration and diafiltration of commercial Savinase® 16L with a 3.5 Kd membrane using CaCl2 5 mM (diafiltration factor of about 50). This method allows the removal of the polyols contained in commercial Savinase®. No carrier was added to liquid composition A, so the film produced with this composition represents a negative control.

[0219] Liquid compositions B and C (LC-B and LC-C) were also obtained by ultrafiltration and diafiltration of commercial liquid form of Savinase® with 3.5Kd membrane using CaCl2 5mM (diafiltration factor about 50). Maltodextrin (Maldex-TEREOS) and gum arabic (INSTANT GUM AA-NEXIRA), respectively, were added to the filtrate in powder form in the same proportion, i.e. about 23% by weight, based on the total weight of the liquid composition, to compare the protective effect of these two carriers. The description of the various liquid compositions is summarized in Table 1.

[0220] [Table 1]

[0221] 1.2-Preparation of master batches using the composition of 1.1 above A masterbatch composition was prepared from polycaprolactone (PCL) polymer pellets (Capa™ 6500 from Perstorp) and the composition of the present invention described in Example 1.1. The enzyme activity of the masterbatch was further determined.

[0222] A compounding machine was used, namely a co-rotating twin screw extruder (Leistritz ZSE 18MAXX). This compounding machine is equipped with nine successive heating zones Z1 to Z9, the temperature of which can be controlled and adjusted independently. Zone Z9 is followed by an additional zone Z10, which is connected to the head of the twin screw (Z10), which is also a heating section. In order to efficiently mix the liquid composition of the invention with the molten polymer, a suitable screw profile was used. The parameters used for each masterbatch to be extruded are summarized in Table 2.

[0223] The molten polymer reached screw Z10 equipped with a die plate with one 3.5 mm hole and was immediately immersed in a 2 m long cold water bath filled with a mixture of water and crushed ice. The resulting extrudate was granulated into solid pellets less than 3 mm in size.

[0224] According to this experiment, 80% by weight of PCL was extruded with 20% by weight of the liquid composition.

[0225] [Table 2]

[0226] The enzyme activity of each masterbatch was determined according to the protocol described below.

[0227] In a 50 mL Falcon tube, 50 mg of pellets were mixed with 10 mL of dichloromethane (Sigma Aldrich, CAS75-09-2). The solution was mixed using a vortex (Genie2-Scientific Industrie) until the compound was completely dissolved. Then, 5 mL of 0.1 M Tris buffer (pH 9.5) was added. Each tube was shaken by hand to create an emulsion. The organic and aqueous phases were then separated by centrifugation (Heraeus Multifuge X302-Thermoscientific) at 10000G for 5 min. The aqueous phase was removed and kept separately. Another 5 mL of 0.1 M Tris buffer (pH 9.5) was added to the organic phase and the protocol was repeated until the aqueous phase was removed. Both 5 mL aqueous phases were mixed. The samples were bubbled with oxygen for 20 min to remove traces of dichloromethane in the 10 mL aqueous phase. The protease activity of each sample was determined using a colorimetric test. 20 μL of the sample at the correct dilution was mixed with 180 μL of 5 mM pNA solution (N-Succinyl-Ala-Ala-Ala-p-nitroanilide, Sigma Aldrich-CAS52299-14-6). The optical density was measured at 30 °C-420 nm using an absorption spectrophotometer (Clariostar-BMG Labtech). The mass of active enzyme was determined using a calibration curve.

[0228] By comparing the mass of active enzyme in the compound with the theoretical enzyme mass it was possible to determine the percentage of residual activity in the masterbatch.

[0229] The residual activity of each masterbatch prepared is summarized in Table 3.

[0230] [Table 3]

[0231] Masterbatches made with liquid compositions LC-B and LC-C exhibited higher residual activity compared to a masterbatch made with a liquid composition without a carrier (LC-A - negative control), indicating a high degree of protection of the enzyme during the extrusion process. The masterbatches made with the composition containing gum arabic exhibited better residual activity compared to the masterbatch made with the composition containing maltodextrin.

[0232] 1.3-Production of the biodegradable plastic film of the present invention The granulated masterbatch composition of Example 1.2 was used to manufacture a biodegradable polylactic acid-based plastic article of the present invention by extrusion. The biodegradability of the plastic article was further tested.

[0233] Preparation of PLA-based matrix The PLA-based matrix was extruded using the twin screw extruder described in Example 1.2 and had the following composition by weight: 42.3% PLA 4043D (NatureWorks), 51.7% PBAT PBE006 (NaturePlast), and 6% CaCO3 (OMYA).

[0234] All materials were dried before extrusion. PLA and PBAT were dried in a desiccator at 60°C and 40°C, respectively, for approximately 16 hours. For calcium carbonate, a vacuum oven at 40°C-40mb was used for 16 hours.

[0235] The temperature of zone 10 of the extruder was set at 185°C. The screw speed was 175 rpm, and the total input mass rate was about 7 kg / h. CaCO3 was introduced into the molten polymer in zone 7 using a gravimetric feeder to obtain a matrix. The resulting extrudate was cooled in a cold water bath and then pelletized.

[0236] Masterbatch The masterbatches MB1-MB2-MB3 described in Example 1.2 are used to produce the plastic film of the present invention.

[0237] Film Blowing Process Prior to film blowing extrusion, the masterbatch and PLA-based matrix were dried in a desiccator at 50° C. for 40 h. Based on the theoretical enzyme mass of the masterbatch according to Table 4, blends were prepared to introduce the same amount of enzyme into all films.

[0238] [Table 4]

[0239] The films were produced using a LabTech Compact Film Blowing Line Model LF-250 equipped with a 20 mm 30 L / D Extruder Model LBE20-30 / C. The screw speed was 50 rpm. The temperature settings are detailed in Table 5.

[0240] [Table 5]

[0241] 1.4-Biodegradability testing Biodegradability tests were carried out using the plastic film produced in Example 1.3 according to the following protocol.

[0242] 100 mg of each film was weighed and placed in a plastic bottle containing 50 mL of 0.1 M Tris buffer (pH 8). Depolymerization was initiated by incubating each sample at 28 °C and 150 rpm in an Infors HT Multitron Pro incubation shaker. Aliquots of 1 mL of buffer were sampled periodically, filtered through a 0.22 μm syringe filter, and the samples were analyzed by high performance liquid chromatography (HPLC) equipped with an Aminex HPX-87H column to monitor the release of lactic acid (LA) and lactate dimer. The chromatography system used was an Ultimate 3000 UHPLC system (Thermo Fisher Scientific, Inc., Waltham, MA, USA) equipped with a pump module, an autosampler, a column oven thermostated at 50 °C, and a UV detector at 220 nm. The eluent was 5 mM H2SO4. 20 μL of sample was injected. LA was measured according to a standard curve constructed from commercially available LA.

[0243] The hydrolysis of the plastic films was calculated based on the liberated LA and LA dimers. The percentage of degradation is calculated with respect to the percentage of PLA in the film.

[0244] The results of depolymerization of the inventive films after 2 days are shown in Table 6.

[0245] [Table 6]

[0246] The films of the invention (MB2 / LC-B and MB3 / LC-C) show a higher depolymerization rate due to a higher residual activity compared to the control film made with a liquid composition without a carrier (MB1 / LC-A - negative control). These results confirm that the use of a liquid composition with a carrier leads to a higher degree of protection of the enzyme during the extrusion process. The films made with the composition containing gum arabic show better degradability compared to the films made with the composition containing maltodextrin.

[0247] Example 2 - Preparation of a liquid composition, use of said composition to make a film of the present invention, and evaluation of the mechanical and degradation properties of said film 2.1- Preparation of compositions containing biological substances Liquid composition LC was prepared from commercially available protease Savinase® 16L (Novozymes). LC was obtained by ultrafiltration and diafiltration of commercially available Savinase® 16L with 3.5Kd membrane using CaCl2 5mM (diafiltration factor about 100) to obtain a concentrated liquid composition and remove polyols present in the commercially available solution. Next, about 23% gum arabic (INSTANT GUM AA-NEXIRA) based on the total weight of the liquid composition was added to the liquid composition (LC) as a carrier.

[0248] A solid composition was also prepared following the same protocol using the commercially available protease Savinase® 16L and the protocol described above. The resulting liquid composition was concentrated and then dried by lyophilization to obtain a solid composition (SC).

[0249] A comparison of the various compositions is summarized in Table 7.

[0250] [Table 7]

[0251] 2.2- Preparation of Masterbatch Masterbatches were prepared using the same compounding machine as in Example 1.2 with polycaprolactone polymer pellets (Perstorp PCL-Capa™ 6500) and the liquid or solid compositions of 2.1.

[0252] More specifically, a masterbatch was prepared containing PCL and the liquid enzyme composition LC of Example 2.1. PCL and LC were introduced separately into the feed zone, which is the unheated zone of the extruder. For feeding, a gravimetric feeder was used for the polymer and a peristaltic pump was used for the liquid composition. The resulting masterbatch was designated MB-L.

[0253] In parallel, a masterbatch was prepared containing PCL and the solid enzyme composition SC of Example 2.1. The SC was introduced into zone 7 using a gravimetric feeder suitable for dosing solids in powder form. The masterbatch obtained was designated MB-S.

[0254] The parameters used for extrusion of the masterbatches are detailed in Tables 8 and 9. Appropriate screw profiles were used to efficiently mix the corresponding compositions with the polymer.

[0255] [Table 8]

[0256] [Table 9]

[0257] The molten polymer reached screw Z10 equipped with a die plate with one 3.5 mm hole and was immediately immersed in a 2 m long cold water bath filled with a mixture of water and crushed ice. The resulting extrudate was granulated into solid pellets less than 3 mm in size.

[0258] 2.3-Preparation of the Film of the Invention Preparation of A-PLA matrix Three different matrices were used to prepare the films: two commercial compounds from BASF, ecovio® F2332 and ecovio® F2223, and a home compounded matrix called matrix 1.

[0259] Matrix 1 was produced using a twin-screw extruder CLEXTRAL EV25HT, which contains 12 zones Z1 to Z12, whose temperatures are controlled and regulated independently. The compound is composed of 33% preplasticized PLA with 10% by weight of tributyl acetyl citrate (CITROFOL® BII ​​from Jungbunzlauer), 32% PBAT Ecoflex C1200 provided by BASF, 30% thermoplastic starch, the starch being standard corn starch 171111 provided by Roquette, and 5% calcium carbonate from OMYA. The starch is introduced in zone 1 and the polymer in zone 6. The zones are heated according to table 10. This compound is called Matrix 1.

[0260] [Table 10]

[0261] B—Production of the Film of the Present Invention Using the Liquid Composition (MB-L) For film blowing, a LabTech compact film blowing line model LF-250 equipped with a 20 mm 30 L / D extruder model LBE20-30 / C was used. The screw speed used was 60 rpm. The film blow ratio was about 5 for the 17 μm target.

[0262] Prior to film blowing, MB-L (Example 2.2) and different PLA-based matrices were dried in a desiccator at 50° C. for 40 h. Then, MB-L was mixed with the PLA-based matrices in a weight ratio of 93 / 7 between PLA and masterbatch.

[0263] The films obtained with the PLA-based matrices ecovio® F2332 and ecovio® F2223 are called film 1 and film 2, respectively, and the parameters used for extrusion are given in Table 11.

[0264] [Table 11]

[0265] The film produced using Matrix 1 is called Film 3 and Table 12 shows the parameters used for extrusion.

[0266] [Table 12]

[0267] C - Preparation of a control film using solid composition (MB-S) Films were produced using the PLA-based matrices ecovio® F2332 and ecovioo® F2223 as well as Matrix 1 and further using a masterbatch containing a solid composition of biological material, designated Film 4, Film 5 and Film 6, respectively.

[0268] Prior to film blowing, the MB-S and PLA-based matrices were dried in a desiccator for 40 hours at 50° C. To obtain the same biological material concentration in all the films of the present invention, an additional masterbatch containing only PCL and gum arabic at 70 / 30 w / w was added to the MB-S / PLA-based matrix mixture.

[0269] Finally, films were prepared using a mixture of 93 wt % PLA-based matrix and 7 wt % of both masterbatches (MB-S and additional masterbatch).

[0270] Films 1 and 4, films 2 and 5, and films 3 and 6 have the same composition, respectively. Then, MB-S was dry-mixed with the PLA-based matrix and introduced into a film-blowing extruder.

[0271] The films were made using the same process as Films 1, 2 and 3, except for the temperature profile shown in Table 13.

[0272] [Table 13]

[0273] 2.4-Evaluation of the mechanical properties and biodegradability of the plastic films of the present invention The inventive film of Example 2.3 was analyzed for the following parameters: A. Hayes The haze is determined using a spectrometer UV-Visible Perkin Elmer 650S equipped with a 150 mm integrating sphere according to NF EN 2155-9 (August 1989). Values ​​are given for a 50 x 30 mm 2 For each film, the measurement is repeated three times on three different parts of the film.

[0274] B. Surface roughness (dynamic friction coefficient) Dynamic friction coefficient (μ D ) is measured according to standard NF EN ISO-8295 (December 2004) which fits plastic films or sheets with a thickness less than 0.5 mm. It is determined using a Lloyd Instruments LS5 testing machine with 20N sensor capacity. The device comprises a horizontal test platform on which the first sample is placed, a mass which exerts a pressing force (1.96N) and to which the second sample is attached, and a traction mechanism which produces a relative movement between the mass and the test platform. The mass is pulled and moved on the test platform (test speed = 500 mm / min). The measurements are accurate to about 0.01%. The sample dimensions are 80 mm x 200 mm.

[0275] Dynamic friction force F D is the average force during the first 6 cm of relative motion.

[0276] C. Mechanical tensile properties and thickness Tensile mechanical properties (elongation at break, tensile stress at break, Young's modulus) were measured using a Zwick testing machine with a 50N sensor capacity according to ASTM D882-12 standard (23°C and 55% RH). Two film directions, machine direction and transverse direction, were analyzed according to the following parameters: - Grip separation speed for Young's modulus = 10 mm / min - Grip separation speed for other properties = 50 mm / min - Initial gripper separation: 100mm - Sample size: 150mm x 15mm - Average thickness: 17μm

[0277] The thickness used for tensile analysis was determined based on the weight, dimensions and density of the film. This choice was made to overcome overestimation of thickness due to the presence of particle agglomerates at the film surface, especially when solid compositions were used.

[0278] Nonetheless, thickness measurements can be made using a Mitutoyo thickness gauge to indicate the surface roughness observed in films containing aggregates.

[0279] D. Depolymerization test The protocol was the same as that used in Example 1.4.

[0280] E. Results and Comparisons The results obtained for films of the present invention made with liquid compositions were compared with the results obtained for films made with solid compositions: Film 1 vs. Film 4, Film 2 vs. Film 5, and Film 3 vs. Film 6.

[0281] - Mechanical properties Table 14 shows the haze results measured for films 1, 2, 4 and 5. The haze values ​​of films 1 and 2 of the present invention are lower than those of films 4 and 5, respectively. Haze is caused by impurities contained in the plastic article, such as the accumulation of small particles in the article or very small defects on the surface. The lower the haze value, the more transparent the article. Thus, the films of the present invention made from the liquid composition show lower haze than the control film, and therefore better dispersion of biological materials.

[0282] [Table 14]

[0283] Tables 15 and 16 show the dynamic friction coefficient, tensile properties, and thickness measured with a Mitutoyo thickness gauge for the films prepared in 2.3. "s" corresponds to the standard deviation in the same units as the measured property.

[0284] [Table 15]

[0285] In Table 16, the film made from MB-S is used as the reference and is considered to be 100% of the defined parameters.

[0286] [Table 16]

[0287] The coefficient of friction is the ratio between the sliding force and the holding force of two surfaces in contact. This coefficient characterizes the difficulty of two materials sliding against each other. This difficulty can increase when the surface is rough. The dynamic friction coefficient values ​​of films 1, 2 and 3 of the present invention are lower than those of films 4, 5 and 6, respectively, indicating lower surface roughness. The use of liquid compositions in the manufacturing process can reduce the dynamic friction coefficient, which can reduce surface roughness compared to the use of solid compositions of biological materials.

[0288] This characteristic is visible to the naked eye, with films 4, 5 and 6 exhibiting surface irregularities due to particle agglomeration.

[0289] Thickness measurements using a Mitutoyo thickness gauge also show that this surface roughness observed for films made from solid compositions of biological materials leads to aggregates in the film.

[0290] The Young's modulus, strain at break and ultimate tensile strength measured for the inventive films are significantly higher than the control films. The liquid composition has a smaller particle size, resulting in a fine and uniform dispersion of the particles in the film, resulting in improved mechanical properties.

[0291] - Depolymerization test The depolymerization tests showed that the films of the present invention had a significantly higher depolymerization rate (%) compared to the films obtained with the solid enzyme composition, as shown in Table 17 (films from ecovio® F2332), Table 18 (films from ecovio® F2223) and Table 19 (films from Matrix 1). The film made from MB-S was used as the reference and considered as 100.

[0292] [Table 17]

[0293] [Table 18]

[0294] [Table 19]

[0295] 2.5-Manufacture of rigid plastic articles An injection molding machine was used for the production of rigid plastic articles: KM50t / 380 CX ClassiX type with MC6 computer controller system.

[0296] Rigid plastic articles were manufactured by incorporating the masterbatch MB-L of example 2.2 in two polyester-based matrices selected from two polylactic acid polymer grades, the properties of which are shown in Table 20.

[0297] [Table 20]

[0298] Prior to dry blending, the polyester matrix and masterbatch were dried in a desiccator at 50°C for 40 hours. Then, 10% MB-L was added to the polyester matrix. For comparison, a product with 100% polyester matrix was also produced.

[0299] Pieces of 60 mm x 60 mm articles with a thickness of 1 mm were produced by injection moulding, with parameters set according to the grade of polyester matrix acid used.

[0300] The parameters set for injection molding are summarized in Table 21.

[0301] [Table 21]

[0302] The total residence time of the compositions in the barrel was measured to be about 12 minutes for PA1 and PA2, and about 13 minutes for PA3 and PA4.

[0303] The produced rigid articles were subjected to depolymerization test according to the protocol described in Example 1.4. The results are shown in Table 22. PA1 and PA3 are used as the reference and are considered to be 100. The results demonstrate that the use of the composition of the present invention allows the production of biodegradable rigid plastic articles.

[0304] [Table 22]

[0305] [Table 23]

[0306] Example 3 - Preparation of a masterbatch using a liquid composition, use of said masterbatch for the manufacture of a PLA-based rigid article of the present invention, and evaluation of the tensile, impact and biodegradation properties of said article 3.1- Preparation of masterbatches using liquid compositions Masterbatches were prepared using polycaprolactone (PCL) polymer pellets (Capa™ 6500 from Perstorp) and the liquid or solid enzyme compositions listed in Table 24. Liquid composition LC-1 and solid composition SC-1 were prepared in the same manner as detailed in Example 2.1.

[0307] [Table 24]

[0308] Masterbatch MB-LC1, containing PCL and liquid composition LC-1, was prepared using a twin-screw extruder Clextral Evolum 25HT, containing 12 zones Z1 to Z12, whose temperatures are independently controlled and regulated. The parameters used for this process are as follows: temperature profile 65°C-65°C-65°C-65°C-65°C-65°C-65°C-65°C-65°C-65°C-65°C-50°C, extruder screw speed 450 rpm, and total flow rate 40 kg / h. Using a volumetric pump, PCL is introduced into zone 1 at 32 kg / h and liquid composition LC-1 is introduced into zone 5 at 8 kg / h. 20% of the liquid enzyme composition was introduced into PCL, based on the total weight of the masterbatch to be extruded.

[0309] In parallel, masterbatch MB-SC1 comprising PCL and solid composition SC-1 was prepared in a co-rotating twin screw extruder (Leistritz ZSE 18MAXX) with the following parameters: temperature profile 70°C-70°C-70°C-70°C-65°C-65°C-65°C-65°C-65°C, screw speed 150 rpm, and total flow rate 2 kg / h. A gravimetric feeder in zone 7 was used to introduce 22% of the solid enzyme composition based on the total weight of the masterbatch into the PCL. The cooling and granulation system for both masterbatches was the same as detailed in Example 1.2.

[0310] Thus, both masterbatches MB-LC1 and MB-SC1 contain the same enzyme concentration.

[0311] 3.2-Production of the rigid plastic of the invention by injection molding Plastic dumbbells with a thickness of 4 mm and a total length of 170 mm were manufactured using an injection molding machine (KM 50t / 380 CX ClassiX).

[0312] Dumbbells were made from injected PLA grade NatureWorks® Ingeo™ 3251D and masterbatch MB-LC1 as described in 3.1. Control dumbbells were made from the same PLA grade and masterbatch MB-SC1 as described in 3.1. 100% PLA dumbbells were also made for standardized mechanical property evaluation.

[0313] Prior to fabricating the rigid articles, PLA and MB-LC1 were dried using a desiccator at 50° C. for 40 h, and MB-SC1 was dried in a vacuum oven at 50° C. for 48 h. Rigid plastic articles were made using 95 wt % PLA-based matrix and 5 wt % masterbatch.

[0314] The injection molding parameters for each article are detailed in Table 25.

[0315] [Table 25]

[0316] 3.3- Tensile and impact property evaluation of plastic articles The tensile and impact properties of the rigid plastic articles of the present invention and control plastic articles made from the solid compositions were evaluated.

[0317] - Tensile Test Tensile tests were performed using a Zwick Roell testing machine equipped with a 20 kN force sensor. The tests were performed according to the ISO 527-1 standard and the results are shown in Table 26.

[0318] [Table 26]

[0319] Rigid articles made from masterbatches derived from the liquid compositions showed no significant differences in the measured mechanical properties, indicating that the use of the liquid composition does not have any significant effect on the modulus, maximum stress, strain at maximum stress, stress at break, and strain at break of the rigid articles of the present invention.

[0320] - Charpy impact test The tests were carried out in accordance with the NF EN ISO179-1 standard using a Zwick pendulum impact tester. Test bars were cut from the injected specimens using heated pliers. The bar dimensions were 4 mm. * 10mm * The test results are shown in Table 27.

[0321] [Table 27]

[0322] Rigid articles of the present invention made from liquid compositions of biological material exhibit superior impact resistance to articles made from solid biological material compositions, no doubt due to the fine dispersion of the biological material in the plastic article.

[0323] 3.4-Depolymerization test: The extruded rigid article RA-LC1 produced from the liquid composition was tested for biodegradability. The rigid article was first coarsely ground and immersed in liquid nitrogen, then ground using an Ultra-Centrifugal Mill ZM 200 RETSCH equipped with a 500 μm grid. 100 mg of this powder was weighed and placed in a dialysis tube and confined. The tube was placed in 50 mL of 0.1 M Tris buffer (pH 9.5). Depolymerization was initiated by incubating each sample at 45° C. and 150 rpm in an Infors HT Multitron Pro incubation shaker. Aliquots of 1 mL of buffer were periodically sampled and filtered through a 0.22 μm syringe filter, and the samples were analyzed by high performance liquid chromatography (HPLC) equipped with an Aminex HPX-87H column to monitor the release of lactic acid (LA) and lactic acid dimer. The chromatographic system used was an Ultimate 3000 UHPLC system (Thermo Fisher Scientific, Inc., Waltham, MA, USA) equipped with a pump module, an autosampler, a column oven thermostated at 50°C, and a UV detector at 220 nm.

[0324] The eluent was 5 mM H2SO4. 20 μL of sample was injected. LA was measured according to a standard curve prepared from commercially available LA.

[0325] The depolymerization level of the hard article was about 10% after 48 hours, indicating that the biological material retains polyester degradation activity in the final plastic article.

[0326] Example 4 - Preparation of a masterbatch using a liquid composition, use of said masterbatch to manufacture a rigid sheet of the present invention, and evaluation of the tensile, impact and degradation properties of said sheet 4.1-Preparation of masterbatches using liquid compositions A masterbatch composition was prepared from polycaprolactone (PCL) polymer pellets (Capa™ 6500 from Perstorp) and the liquid enzyme composition LC-1 described in Example 3.1. The masterbatch was produced using a co-rotating twin-screw extruder CLEXTRAL EV25HT containing 12 zones Z1-Z12 whose temperatures were independently controlled and regulated.

[0327] Using volumetric pumps, PCL is introduced into zone 1 at 16 kg / h and the liquid composition is introduced into zone 5 at 4 kg / h. Each zone is heated according to table 27. 20% of the liquid composition LC, based on the total weight of the masterbatch, is introduced into the PCL. This masterbatch is called MB-LC2.

[0328] [Table 28]

[0329] The enzyme activity of the masterbatches was determined according to the protocol described in Example 1.2. By comparing the mass of active enzyme in the masterbatch with the theoretical enzyme mass, it was possible to determine the percentage of residual activity in the masterbatch.

[0330] 4.2-Manufacture of the biodegradable plastic sheet of the present invention Thermoformable PLA grade Total Corbion Luminy® LX175 was used to further manufacture 450 μm thick plastic sheets that were subjected to standardized impact and tensile property evaluation and biodegradability testing.

[0331] For plastic sheet production, an extruder FAIREX was used, equipped with four zones Z1-Z4 with a diameter of 45 mm, a 220 mm flat die with an adjustable lip with a nominal opening of 1.5 mm, and a three-cylinder calender, whose temperature was independently controlled and regulated.

[0332] Prior to extrusion and calendaring, MB-LC2 and PLA were dried and mixed together. MB-LC2 was dried in a vacuum oven at 40° C. for 20 hours, and PLA was dried in a dryer at 40° C. for 4 hours.

[0333] The sheets obtained from PLA with 0% (negative control), 5% or 10% MB-LC2 loading were designated S0, S5 and S10, respectively. The extrusion and calendaring parameters are detailed in Table 28.

[0334] [Table 29]

[0335] 4.3-Evaluation of biodegradability of plastic sheets To evaluate the biodegradability of the plastic sheets, depolymerization tests were performed according to the protocol described in Example 3.4.

[0336] After 8 days, powders from sheets S0, S5 and S10 showed depolymerization rates of 0.08%, 0.77% and 13.0% PLA, respectively, indicating that the biological material retains polyester degradation activity in the final plastic articles of the present invention (S5 and S10).

[0337] 4.4-Dart test characterization of plastic sheets The impact tests were carried out according to NF EN ISO7765-1 using the step method. According to this standard the specimens are cut directly on the plastic sheet. The tests were carried out using a Labthink BMC-B1 Dart Tester and the results are shown in Table 29.

[0338] [Table 30]

[0339] The impact test results show that the inventive sheets (S5 and S10) made from the liquid compositions exhibit improved impact resistance compared to the control S0 made from 100% PLA.

[0340] 4.5- Tensile property evaluation of plastic sheets Tensile tests were carried out using a Zwick Roell testing machine equipped with a 20 kN force sensor. Tests were carried out according to standard NF EN ISO 527-1. The measured tensile properties are shown in Table 30.

[0341] [Table 31]

[0342] Compared to pure PLA sheets (S0), sheets made from the masterbatch itself made from the liquid composition and PCL show improved flexibility while maintaining sufficient stiffness required for the intended application due to increased incorporation of the masterbatch into the PLA-based sheet.

[0343] Example 5 - Preparation of a masterbatch using a liquid composition and use of said masterbatch for the manufacture of a film of the present invention containing PCL and PLA 5.1- Preparation of liquid compositions Various liquid compositions were prepared using Savinase® 16L (Novozymes), a commercially available protease sold in liquid form.

[0344] Liquid compositions D, E, F and G are obtained according to the method described in Example 1.1: ultrafiltration and diafiltration of commercial Savinase® 16L on a 3.5 Kd membrane, in which gum arabic is added as a carrier. Commercial Savinase® 16L sold in liquid form corresponds to liquid composition H and is used as a negative control. This composition comprises more than 50% by weight of a polyol, based on the total weight of the liquid composition and water, as a carrier.

[0345] A description of the various liquid compositions is summarized in Table 31.

[0346] [Table 32]

[0347] 5.2 - Preparation of master batches using the composition of 5.1 above A masterbatch composition was prepared from polycaprolactone (PCL) polymer pellets (Perstorp Capa™ 6500) and the composition described in Example 3.1 using the same compounding machine as in Example 1.2.

[0348] According to this experiment, 80% by weight of PCL was extruded with 20% by weight of the liquid composition. The parameters used for each extruded masterbatch are summarized in Table 32.

[0349] [Table 33]

[0350] The enzyme activity of the masterbatches was further determined using the protocol described in Example 1.2. By comparing the mass of active enzyme in the masterbatch with the theoretical enzyme mass, the percentage of residual activity in the masterbatch could be determined. The residual activity of the produced masterbatches is summarized in Table 33.

[0351] [Table 34]

[0352] All masterbatches made with the liquid compositions (LC-D-LC-G) show high residual activity, whereas MB8, the negative control containing Savinase 16L, shows no residual activity. This result supports the value of the liquid compositions with specific carriers in the extrusion process compared to the commercial formulations described above.

[0353] MB5 and MB7, which have similar moisture contents (or similar dry matter) but different biological material contents, show comparable residual activity. This result tends to indicate that the protection of biological material is comparable, regardless of the proportion of biological material involved.

[0354] Furthermore, MB4, produced from the composition containing the highest amount of water, exhibits the lowest residual activity compared to the compositions used to produce MB5, MB6, or MB7.The results tend to indicate that, independent of the amount of biological material introduced into the liquid composition, protection of the biological material is increased when the amount of aqueous solvent is less than 70%, preferably less than 60%, and / or the amount of dry matter is greater than 30%, preferably greater than 40%.

[0355] 5.3-Production of the biodegradable plastic film of the present invention The granulated master batch compositions MB4, MB5 and MB6 of Example 5.2 were used to manufacture biodegradable polylactic acid-based plastic articles of the present invention by extrusion, and the biodegradability of the plastic articles was tested.

[0356] Preparation of PLA-based matrix The PLA-based matrix was extruded using the twin screw extruder described in Example 1.2. The composition of the matrix was 42.3 wt% PLA 4043D from NatureWorks, 51.7 wt% PBAT PBE006 from NaturePlast, and 6 wt% CaCO3 from OMYA. All materials were dried before extrusion. PLA and PBAT were dried in a desiccator at 60°C and 40°C, respectively, for approximately 5 hours. For calcium carbonate, a vacuum oven at 40°C-40mb was used for 16 hours.

[0357] The temperature of zone 10 of the extruder was set at 185°C. The screw speed was 175 rpm, and the total input mass rate was about 5 kg / h. CaCO3 was introduced into the molten polymer in zone 7 using a gravimetric feeder to obtain a PLA-based matrix. The resulting extrudate was cooled in a cold water bath and then pelletized.

[0358] Masterbatch The masterbatches MB4-MB5-MB6 described in Example 5.2 are used to produce the plastic film of the present invention.

[0359] Film Blowing Process Prior to film blowing extrusion, the masterbatch and PLA-based matrix were dried in a vacuum oven at 50°C-40mb for 15 hours. Blends were prepared to introduce the same amount of enzyme in all films based on the theoretical enzyme mass of the masterbatch according to Table 34. Films E and F required the addition of PCL6500 (and dried according to the same conditions) to obtain the same composition in all films.

[0360] [Table 35]

[0361] Blowing was carried out using the same machine and parameters as described in Example 1.3.

[0362] 5.4-Biodegradability testing The plastic film produced in Example 5.3 was tested for biodegradability according to the protocol described in Example 1.4.

[0363] The hydrolysis of the plastic films was calculated based on the liberated LA and LA dimers. The percentage of degradation is calculated with respect to the percentage of PLA in the film.

[0364] The depolymerization results of the films after 4 days are shown in Table 35.

[0365] [Table 36]

[0366] All the films of the present invention show high depolymerization rates, indicating the presence of active enzymes. The higher the dry matter content of the liquid formulation, the higher the decomposition yield is achieved in the films of the present invention. This result confirms that the higher dry matter content in the compositions of the present invention provides a higher degree of protection of biological materials during both extrusion processes (masterbatch production and plastic article production).

[0367] Example 6 - Preparation of a masterbatch using a liquid composition and use of said masterbatch for the manufacture of a film of the present invention containing PLA 6.1-Preparation of masterbatches using the composition of the present invention and PLA, and evaluation of the residual activity of said masterbatches Liquid composition LC-1 from Example 3.1 and two grades of polylactic acid (PLA) were used to prepare the masterbatch: amorphous grade Luminy LX930U from Total Corbion (melting temperature below 140° C.) and semi-crystalline grade Ingeo™ Biopolymer 4043D from NatureWorks (melting temperature above 140° C.).

[0368] Polylactic acid-based masterbatches, designated MB-PLA1, MB-PLA2 and MB-PLA3, were prepared in a co-rotating twin-screw extruder (Leistritz ZSE 18MAXX) with a screw speed of 150 rpm and a total flow rate of 2 kg / h. The extruder temperatures are detailed in Table 36 below. PLA was introduced into the unheated feed zone (Z0) and LC-1 into Z6 using a Brabender pump. The cooling and granulation system for both masterbatches was the same as detailed in Example 1.2. The compositions of the masterbatches are also shown in Table 36.

[0369] [Table 37]

[0370] Following the protocol set out in Example 3.4, the masterbatches prepared above were used to carry out biodegradation tests and the depolymerization levels after 24 hours are shown in Table 37.

[0371] [Table 38]

[0372] The masterbatches (MB-PLA1 and MB-PLA2) based on PLA LX930U with a low melting point showed higher depolymerization levels than MB-PLA3 based on PLA4043D, where a higher extrusion temperature was used (even with an equivalent amount of biological material). Thus, the enzyme activity of liquid composition LC-1 is significantly better maintained at lower process temperatures using PLA with a melting temperature below 140°C.

[0373] 6.2-Film preparation and biodegradability evaluation MB-PLA1 or MB-PLA2 and PLA-based matrix from Example 1.3 (42.3 wt% PLA 4043D from NatureWorks, 51.7 wt% PBAT PBE006 from NaturePlast, and 6 wt% CaCO3 from OMYA) were used to prepare films. Prior to film blowing extrusion, the master batch and PLA-based matrix were dried in a vacuum oven at 60°C for 5 hours. The compositions of the prepared blends are shown in Table 38.

[0374] [Table 39]

[0375] The film blowing line and temperature settings used were the same as in Example 1.3. The screw speed was set at 60 rpm. The amplitude and suction speed of the cooling air were adjusted to obtain a bubble with a width of 200 mm and a film thickness of 15-20 μm.

[0376] The films prepared above were tested for biodegradability according to the protocol set out in Example 1.4 and the depolymerization levels after 26 days are shown in Table 39.

[0377] [Table 40]

[0378] All films made from masterbatches containing PLA with melting temperatures below 140° C. and compositions of the invention showed degradation in aqueous media. Films 7 and 9 are assumed to contain the same amount of biological material, but film 7 based on the most concentrated masterbatch (MB-PLA1 made from 20% LC-1) shows a higher degradation level than film 9 based on MB-PLA2 made from 10% LC-1. However, the results show that the liquid compositions of the invention are also suitable for being introduced into partially or completely molten polymers with melting points above 140° C., and that the biological material still retains polymer degradation activity in the masterbatch.

[0379] Example 7 - 3D printing production of rigid plastic articles of the present invention including PLA and PCL 7.1-Preparation of masterbatches using liquid compositions and evaluation of the residual activity of said masterbatches Liquid composition LC-1 from Example 3.1 was used to prepare a masterbatch. Using the same extruder and the same parameters as in Example 1.2, a masterbatch was prepared, designated MB9, consisting of 90% PCL (Capa™ 6500 from Perstorp) and 10% liquid composition LC-1 (screw speed was set at 150 rpm, total flow rate at 2 kg / h).

[0380] The enzyme activity of the masterbatch was determined according to the protocol described in Example 1.2. The residual activity of MB9 is 87%.

[0381] 7.2 Filament Manufacturing and 3D Printing of Rigid Plastic Articles Including PLA and PCL PLA-based filaments were produced using Ingeo™ Biopolymer 4043D from NatureWorks. Masterbatch MB9 and PLA were dried in a vacuum oven at 50°C for 15 hours before extruding the filaments. The masterbatch was dry mixed with PLA at a weight ratio of 30% / 70% and then extruded into a single screw extruder (Scamex-Rheoscam, φ20-11L / D) at 100°C-170°C-190°C settings in three zones of the extruder and 180°C setting at the die. A screw speed of 47 rpm was used. The extrudate was cooled with compressed air and the final diameter of the filament was approximately 1.75 mm.

[0382] A Cartesian printer was used. The Neocore model has a 30x30cm basalt plateau that can be heated up to 200°C and a single nozzle E3D with a BondTech filament system that can be heated up to 400°C. 3D printing tests were performed using a 5A tensile specimen geometry according to ISO537-2. The 3D printing parameters are detailed in Table 40.

[0383] [Table 41]

[0384] 7.3 Depolymerization test Depolymerization tests were performed on 100 mg of micronized 5A tensile specimens (1 mm grid) using the same protocol as in Example 3.4. The depolymerization of the specimens reaches 11% after 8 days in a buffer solution of pH 9.5 at 45° C. (dialysis system). The depolymerization results confirm that biological materials retain polymer decomposition activity in 3D printed plastic articles made from the compositions of the present invention, even after a second heating at high temperature during 3D printing.

Claims

1. 1. A method for preparing a plastic article comprising at least one polyester and a biological material having polyester-degrading activity uniformly dispersed in the plastic article, the method comprising the steps of: (a) mixing 0.01% to 10% by weight of the biological material having polyester-degrading activity with the at least one polyester; and (b) molding the mixture of step (a) into a plastic article; 1. A method according to claim 1 , characterized in that in step (a) the biological material is mixed in the form of a liquid composition comprising the biological material, a polysaccharide carrier selected from natural gums and water in order to uniformly distribute the biological material in the plastic article.

2. 1. A method for preparing a plastic article comprising at least one polyester and a biological material having polyester-degrading activity uniformly dispersed in the plastic article, the method comprising the steps of: (a) mixing 0.01% to 10% by weight of the biological material having polyester-degrading activity with the at least one polyester; and (b) molding the mixture of step (a) into a plastic article; In step (a), in order to uniformly disperse the biological material in the plastic article, the biological material is mixed in the form of a masterbatch comprising the biological material and a carrier polymer having a melting temperature of less than 140° C. and / or a glass transition temperature of less than 70° C., and the biological material is provided in the form of a liquid composition; The masterbatch is prepared by introducing a liquid composition of the biological material into the carrier polymer; 13. The method of claim 12, wherein the liquid composition of biological material further comprises a polysaccharide carrier selected from natural gums and water.

3. 3. The method of claim 1 or 2, wherein the mixing step (a) is carried out at a temperature at which the polyester is in a partially or completely molten state and / or in an extruder.

4. The method of any one of claims 1 to 3, wherein the polyester has a melting temperature above 140°C.

5. The method according to any one of claims 1 to 4, wherein the polyester is chosen from copolymers of lactic acid and / or succinic acid and / or terephthalic acid.

6. 3. The method of claim 2, wherein the carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C is selected from polyester, starch, EVA and mixtures thereof.

7. 7. The method of claim 6, wherein the carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C is a polyester selected from polycaprolactone (PCL), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), polydioxanone (PDS), polyhydroxyalkanoate (PHA), polylactic acid (PLA) and mixtures thereof.

8. 7. The method of claim 6, wherein the carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C is selected from polycaprolactone (PCL), PBAT, PLA, EVA and mixtures thereof.

9. A method according to any one of claims 1 to 8, wherein the natural gum is selected from gum arabic, guar gum, gum tragacanth, gum karaya and mixtures thereof.

10. 1. A method for improving the dispersion uniformity of a biological material in a plastic article comprising at least one polyester, a biological material having polyester degrading activity, a polysaccharide carrier selected from natural gums, and optionally a carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C, the method comprising introducing the biological material in the form of a liquid composition comprising the biological material, the polysaccharide carrier and water, or in the form of a masterbatch prepared by introducing a liquid composition comprising the biological material into the carrier polymer, during the manufacturing process of the plastic article.

11. 11. The method of claim 10, wherein the natural gum is selected from gum arabic, guar gum, gum tragacanth, gum karaya and mixtures thereof.

12. 1. A masterbatch comprising a biological material having polyester degrading activity, a polysaccharide carrier selected from natural gums, and a carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C, the masterbatch being prepared by introducing a liquid composition of the biological material into the carrier polymer.

13. 13. The masterbatch of claim 12, wherein the liquid composition of biological material further comprises a polysaccharide carrier selected from natural gums and an aqueous solvent.

14. The liquid composition comprises, based on the total weight of the composition: - 0.01% to 35% by weight of biological material, - from 15% to 95% by weight of an aqueous solvent, - 3% to 80% by weight of a polysaccharide carrier chosen from natural gums; 14. The masterbatch of claim 13 comprising:

15. 15. The masterbatch according to any one of claims 12 to 14, wherein the carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C is selected from polyester, starch, EVA and mixtures thereof.

16. 16. The masterbatch of claim 15, wherein the polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C is a polyester selected from polycaprolactone (PCL), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), polydioxanone (PDS), polyhydroxyalkanoates (PHA), polylactic acid (PLA) and mixtures thereof.

17. 16. The masterbatch according to claim 15, wherein the polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C is selected from polycaprolactone (PCL), EVA, PBAT, PLA and mixtures thereof.

18. 18. The masterbatch according to any one of claims 12 to 17, comprising 50% to 95% by weight, based on the total weight of the masterbatch, of a carrier polymer having a melting temperature of less than 140°C and / or a glass transition temperature of less than 70°C.

19. 19. The masterbatch of claim 18, comprising 70% to 90% by weight of a carrier polymer having a melting temperature below 140°C and / or a glass transition temperature below 70°C.

20. The masterbatch according to any one of claims 12 to 19, wherein the biological material comprises at least an enzyme having polyester degrading activity.

21. A masterbatch according to any one of claims 12 to 20, wherein the natural gum is selected from gum arabic, guar gum, gum tragacanth, gum karaya and mixtures thereof.

Citation Information

Patent Citations

  • Masterbatch composition comprising a high concentration of biological entities

    WO2016198650A1

  • Biodegradable polyester composition and uses thereof

    WO2016198652A1